Rubber-bonded cellulose fiber and method for producing same, resin composition and method for producing same, and cured resin composition
By bonding small-particle rubber particles and silane compounds on the surface of cellulose fibers, the problem of high viscosity of epoxy compounds and cellulose fiber resin compositions is solved, and a resin composition with low viscosity is realized, which is suitable for the production of various composite materials.
Patent Information
- Application Number
- CN202380061387.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-31
- Filing Date
- 2023-08-29
- Publication Date
- 2025-04-04
AI Technical Summary
In the prior art, the resin composition containing epoxy compounds and cellulose fibers has high viscosity, making it difficult to form a composite material, and the viscosity further increases after adding rubber particles, resulting in difficult processing.
Rubber bonded cellulose fibers including cellulose fibers, rubber particles having an average particle size of 300 nm or less, and silane compounds are used to bond the rubber particles to cellulose fibers through the silane compound to reduce viscosity and improve mixing uniformity.
A resin composition with low viscosity is achieved, easy to process and apply to various composite materials, and does not easily increase the viscosity during melt-kneading, thereby improving the operability and performance of the composite material.
Smart Images

Figure CN119768439A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to rubber-bonded cellulose fibers and a method for producing the same, a resin composition and a method for producing the same, and a cured resin composition. Background Art
[0002] Composite materials including resin and reinforcing materials are lightweight and high in strength, and therefore are widely used in various industrial fields. In addition, in recent years, attempts have been made to replace conventional materials with materials derived from biomass to reduce emissions of global warming gases.
[0003] As one of the materials derived from biomass, cellulose fiber is known. If epoxy resin and cellulose fiber are combined, a composite material with light weight and high strength is obtained. However, this composite material is sometimes brittle, and the addition of particles with elasticity (such as rubber particles) has been studied (for example, Patent Document 1).
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2015-48375 Summary of the invention
[0007] Problem that the invention aims to solve
[0008] However, the resin composition containing an epoxy compound and cellulose fibers, and the resin composition further containing rubber particles, has a problem that the viscosity is high and it is difficult to form a composite material. The reason for this is considered to be as follows.
[0009] In a resin composition comprising an epoxy compound and cellulose fibers, the cellulose fibers are easy to interact with each other. Moreover, the cellulose fibers form a network through hydrogen bonds, or are physically entangled with each other, thereby increasing the viscosity of the composition. On the other hand, in a resin composition comprising an epoxy compound, cellulose fibers and rubber particles, the interaction between the cellulose fibers is suppressed by the rubber particles entering between the cellulose fibers. However, in this scheme, the viscosity increases due to friction between the free rubber particles in the system. Therefore, it is very difficult to reduce the viscosity of a resin composition comprising an epoxy compound and cellulose fibers.
[0010] In addition, in recent years, research has been conducted on adding cellulose fibers to various resins other than epoxy resins to improve their strength, etc. However, when the resin and cellulose fibers are uniformly mixed by melt kneading, the cellulose fibers are hydrogen-bonded or physically entangled with each other, which easily increases the melt viscosity.
[0011] The present invention has been made in view of the above circumstances, and its object is to provide a resin composition containing an epoxy compound and cellulose fibers and having low viscosity, a method for producing the same, and a cured resin composition as a cured product of the resin composition. In addition, the present invention also aims to provide a rubber-bonded cellulose fiber whose viscosity and melt viscosity are not easily increased when added to various resins, a method for producing the same, and a resin composition containing the rubber-bonded cellulose fiber.
[0012] Solutions for solving problems
[0013] The present invention provides a rubber-bonded cellulose fiber comprising a cellulose fiber, a plurality of rubber particles having an average particle size of 300 nm or less and arranged on the surface of the cellulose fiber, and a silane compound bonding the cellulose fiber and the rubber particles.
[0014] The present invention also provides a resin composition comprising a resin and a fibrous composite derived from the rubber-bonded cellulose fibers.
[0015] The present invention provides a resin composition comprising an alicyclic epoxy compound, cellulose fibers, rubber particles having carboxyl groups on the surface and an average particle size of 300 nm or less, and a silane compound having an amino group.
[0016] The present invention further provides a curable resin composition obtained by curing the alicyclic epoxy compound of the above resin composition with a difunctional active hydrogen compound.
[0017] The present invention also provides a method for producing a resin composition, comprising: mixing an alicyclic epoxy compound, rubber particles having an average particle size of 300 nm or less and having carboxyl groups on the surface, and a silane compound having an amino group; and further mixing cellulose fibers.
[0018] Furthermore, the present invention provides a method for producing rubber-bonded cellulose fibers, the method comprising: a step of mixing a dispersion medium, rubber particles having an average particle size of 300 nm or less and having carboxyl groups on the surface, a silane compound having an amino group, and cellulose fibers to obtain a mixed solution; and a step of removing the dispersion medium from the mixed solution.
[0019] Beneficial Effects
[0020] The resin composition of the present invention comprising an alicyclic epoxy compound comprises an epoxy compound and cellulose fibers, but its viscosity is relatively low. Therefore, it is easy to handle and easy to apply to various composite materials. In addition, the cured resin composition obtained by curing the resin composition with a difunctional active hydrogen compound exhibits thermoplasticity. Therefore, the curable resin composition can be used for various purposes alone or mixed with various thermoplastic resins.
[0021] Furthermore, the rubber-bonded cellulose fiber of the present invention is easy and simple to manufacture. Furthermore, when the rubber-bonded cellulose fiber is mixed or melt-kneaded with various resins, the viscosity and melt viscosity of the rubber-bonded cellulose fiber are not easily increased. Therefore, the rubber-bonded cellulose fiber is easy to handle and can be easily applied to various composite materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 These are photographs of the curable resin compositions prepared in Examples 1 and 12 before being tested for the presence or absence of thermoplasticity.
[0023] Figure 2 These are photographs of the curable resin compositions prepared in Examples 1 and 12 after being tested for the presence or absence of thermoplasticity.
[0024] Figure 3 This is a photograph of the cured resin composition prepared in Example 1 observed with a scanning electron microscope.
[0025] Figure 4 This is a photograph obtained by observing the second resin composition prepared in Example a using a scanning electron microscope.
[0026] Figure 5 These are photographs of the cellulose fibers alone used in Example b and the rubber-bonded cellulose fibers (Example b) obtained from the cellulose fibers. DETAILED DESCRIPTION
[0027] Hereinafter, a first resin composition including an alicyclic epoxy resin and cellulose fibers, a method for preparing the first resin composition, and a cured resin composition obtained from the first resin composition are described. Then, a rubber-bonded cellulose fiber having rubber particles bonded to the surface of the cellulose fiber, and a second resin composition including a fibrous composite derived from the rubber-bonded cellulose fiber are described.
[0028] 1. First resin composition
[0029] The first resin composition of the present invention comprises an alicyclic epoxy compound, cellulose fibers, rubber particles having an average particle size of less than 300nm with a carboxyl group on the surface, and a silane compound having an amino group. In the first resin composition of the present application, the amino group of the silane compound reacts with the carboxyl group of the rubber particles, and the rubber particles and the silane compound are bonded. On the other hand, the Si group of the silane compound is bonded with the OH group of the cellulose fiber to form a siloxane bond, or the OH group of the silane compound is hydrogen-bonded with the OH group of the cellulose fiber, and the silane compound and the cellulose fiber are also bonded. That is, the cellulose fibers and the rubber particles are in a state of being bonded via the silane compound. Moreover, in the first resin composition, the cellulose fibers are not easy to interact with each other, and free rubber particles are not easy to be generated. Therefore, despite the inclusion of cellulose fibers and rubber particles, the viscosity of the first resin composition also falls within the desired range. It should be noted that the description of "including alicyclic epoxy compounds, cellulose fibers, rubber particles and silane compounds" in this specification not only includes the state of including these components separately, but also includes the state of cellulose fibers, rubber particles and silane compounds being compounded through the above-mentioned reaction.
[0030] Here, if a general epoxy compound is mixed with a compound having an amino group, the epoxy compound and the amino group will react, and viscosity increase is likely to occur. However, in the first resin composition of the present invention, an alicyclic epoxy compound that hardly reacts with the amino group is used as the epoxy compound. Therefore, in the first resin composition, the viscosity is made to fall within a desired range. Below, each component of the first resin composition of the present invention is described separately.
[0031] Alicyclic epoxy compounds
[0032] The alicyclic epoxy compound is a resin having an alicyclic structure and an epoxy group consisting of two carbon atoms and an oxygen atom adjacent to the alicyclic structure (also referred to as an "alicyclic epoxy group" in this specification) in the molecular structure. The alicyclic epoxy compound only needs to contain at least one alicyclic epoxy group, but from the perspective of curing the first resin composition for use, it is preferably composed of two or more alicyclic epoxy groups. As described later, in the case where the first resin composition (alicyclic epoxy compound) is cured by a curing agent such as an acid anhydride to form a thermosetting cured resin composition, the alicyclic epoxy compound only needs to have two or more alicyclic epoxy groups, and may also have three or more. On the other hand, in the case where the first resin composition (alicyclic epoxy compound) is cured with a difunctional active hydrogen compound to form a thermoplastic cured resin composition, the alicyclic epoxy compound preferably has only two alicyclic epoxy groups. The first resin composition may contain only one alicyclic epoxy compound, or may contain two or more alicyclic epoxy compounds.
[0033] Examples of the alicyclic epoxy group include an epoxycyclohexyl group, an epoxycyclopentyl group, etc. Examples of the compound having an alicyclic epoxy group include a compound represented by the following formula (i).
[0034] [Chemical formula 1]
[0035]
[0036] In the above formula (i), X represents a single bond or a linking group. Examples of linking groups include divalent hydrocarbon groups, carbonyl groups, ether bonds, ester bonds, siloxane bonds, carbonate groups, amide groups, and groups formed by connecting multiple of them. It should be noted that the epoxycyclohexane group in formula (i) may also be bonded with a substituent (e.g., an alkyl group, etc.).
[0037] Examples of the divalent hydrocarbon group include linear or branched alkylene groups and divalent alicyclic hydrocarbon groups having 1 to 18 carbon atoms. Examples of the linear or branched alkylene groups having 1 to 18 carbon atoms include methylene, methylmethylene, dimethylmethylene, ethylene, propylene, and trimethylene.
[0038] Examples of the divalent alicyclic hydrocarbon group include cycloalkylenes (including cycloalkylidenes) such as 1,2-cyclopentylene, 1,3-cyclopentylene, cyclopentylidene, 1,2-cyclohexylene, 1,3-cyclohexylene, 1,4-cyclohexylene and cyclohexylene.
[0039] Examples of compounds represented by formula (i) include (3,4,3',4'-diepoxy)bicyclohexane, bis(3,4-epoxycyclohexylmethyl)ether, 2,2-bis(3,4-epoxycyclohexane-1-yl)propane, 1,2-bis(3,4-epoxycyclohexane-1-yl)ethane, and compounds represented by the following formulas (i-1) to (i-9). In the following formulas (i-5) and (i-7), l and m each represent an integer from 1 to 30. In the following formula (i-5), R' is an alkylene group having 1 to 8 carbon atoms, among which a linear or branched alkylene group having 1 to 3 carbon atoms, such as a methylene group, an ethylene group, a propylene group, and an isopropylene group, is preferred.
[0040] [Chemical formula 2]
[0041]
[0042] Examples of the alicyclic epoxy compound include the following compounds in addition to the compound represented by the above formula (i).
[0043] [Chemical formula 3]
[0044]
[0045] The epoxy equivalent of the alicyclic epoxy compound is not particularly limited, but is preferably 70 to 200 g / eq, more preferably 80 to 140 g / eq, when curing is performed with an active hydrogen compound described below. The epoxy equivalent can be measured according to JIS K 7236.
[0046] The amount of the alicyclic epoxy compound in the first resin composition is appropriately selected according to the purpose, preferably 1% by mass or more and 95% by mass or less of the first resin composition (when the first resin composition contains a volatile component, it is the non-volatile component of the first resin composition), and more preferably 70% by mass or more and 90% by mass or less. If the amount of the alicyclic epoxy compound is more than 1% by mass, it is easy to use the first resin composition for various purposes. On the other hand, if the amount of the alicyclic epoxy compound is less than 95% by mass, the amount of cellulose fibers, rubber particles, etc. is relatively sufficient, and the strength, toughness, etc. of the cured product of the first resin composition are easy to become good.
[0047] Cellulose fiber
[0048] The cellulose fibers used in the present invention may be fibrous fibers containing cellulose, and may partially contain components other than cellulose, such as hemicellulose and lignin.
[0049] The raw material of the cellulose fiber is not particularly limited, and examples of the raw material include: pulp obtained from wood, bamboo, hemp, jute, kenaf, cotton, sugar beet, agricultural product waste, cloth, etc.; recycled materials such as rayon and cellophane. In addition, the above pulp can also be chemical pulp obtained by chemically or mechanically treating plant raw materials. Specifically, it can be any pulp such as sulfite pulp, semi-chemical pulp, chemical grinding pulp, chemical mechanical pulp, wood pulp, refined mechanical pulp, thermomechanical pulp, chemical thermomechanical pulp, deinked waste paper pulp, corrugated paper waste paper pulp, magazine waste paper pulp, etc. The first resin composition can contain only one type of cellulose fiber, or it can contain two or more types of cellulose fibers.
[0050] The average fiber diameter of the cellulose fiber is preferably 0.02 μm or more and 500 μm or less, more preferably 1 μm or more and 100 μm or less, and particularly preferably 5 μm or more and 60 μm or less. If the average fiber diameter of the cellulose fiber is 1 μm or more and 100 μm or less, it can be obtained more cheaply and has good operability. In addition, the average fiber length of the cellulose fiber that can be used in this process is preferably 0.1 μm or more and 10000 μm or less, preferably 10 μm or more and 5000 μm or less, and more preferably 100 μm or more and 300 μm or less. If the average fiber length of the cellulose fiber is 10 μm or more and 5000 μm or less, it can be obtained more cheaply and has good operability. If the average fiber diameter and average fiber length of the cellulose fiber are within the above range, it is easy to disperse the cellulose fiber in the above-mentioned alicyclic epoxy compound. It should be noted that the above average fiber diameter and fiber length vary depending on the diameter measured, and are average values obtained by measuring the fiber diameters and fiber lengths of more than 100 cellulose fibers by observation using an optical microscope, an electron microscope, AFM, etc. In addition, the higher the ratio of the above average fiber diameter to the average fiber length, i.e., the so-called aspect ratio (average fiber length / average fiber diameter), the easier it is to improve the fracture toughness value.
[0051] As a method for evaluating the aspect ratio of cellulose fibers, there is a viscosity measurement of a cellulose fiber dispersion. The higher the aspect ratio, the more contact between cellulose fibers increases, and the higher the viscosity. Cellulose fibers are added to RKB-5810 (manufactured by RESINOUS KASEI) as a highly transparent rubber-modified epoxy resin, and the concentration is adjusted with Celloxide 2021P (manufactured by Daicel) as an alicyclic epoxy resin. The dispersion viscosity when the rubber particle concentration is 8% by mass and the cellulose fiber concentration is 8% by mass is preferably a cellulose fiber with an aspect ratio of 5Pa·s or more and 300Pa·s or less, and more preferably a cellulose fiber with an aspect ratio of 10Pa or more, 10Pa·s or more and 100Pa·s or less. It should be noted that the lower limit may also be 50Pa·s. According to the cellulose fiber having an aspect ratio that can satisfy the above-mentioned viscosity range, the fracture toughness value is easily improved and the fluidity becomes good. It should be noted that the viscosity measurement conditions are the same as the viscosity evaluation described later.
[0052] The amount of cellulose fiber in the first resin composition is appropriately selected according to the purpose, preferably 1% by mass or more and 10% by mass or less of the first resin composition (when the first resin composition contains volatile components, it is the non-volatile component of the first resin composition), more preferably 2% by mass or more and 8% by mass or less, and particularly preferably 4% by mass or more and 6% by mass or less. If the amount of cellulose fiber is more than 1% by mass, it is easy to play the effect of adding cellulose fiber, for example, the strength of the cured product of the first resin composition increases. On the other hand, if the amount of cellulose fiber is less than 10% by mass, the viscosity of the first resin composition easily falls within the desired range.
[0053] Rubber particles
[0054] The rubber particles can be particles containing rubber and having carboxyl groups on the surface with an average particle size of 300 nm or less. If the first resin composition contains rubber particles having such an average particle size, as described above, it can not only suppress the interaction between the cellulose fibers, but also improve the toughness of the cured product of the first resin composition. The first resin composition can contain only one type of rubber particles, or two or more types of rubber particles.
[0055] The rubber particles may be particles consisting of a single composition, or may be core-shell particles in which a core and a shell component cover part or all of the core. In core-shell particles, for example, the core may contain rubber and the shell may contain a resin having a carboxyl group. It should be noted that core-shell particles are preferred from the viewpoint of easily obtaining desired physical properties by adjusting the amount of carboxyl groups on the surface and the combination of the core and the shell. Hereinafter, the core-shell type is used as an example to illustrate the rubber particles, but is not limited to this scheme.
[0056] Examples of components constituting the core of the core-shell type particles include elastomers mainly composed of polybutadiene, polyisoprene, butadiene-acrylonitrile copolymers, styrene-butadiene copolymers, styrene-isoprene copolymers, ethylene-propylene copolymers, ethylene-α-olefin copolymers, ethylene-α-olefin-polyene copolymers, acrylic rubber, butadiene-(meth)acrylate copolymers, styrene-butadiene block copolymers, styrene-isoprene block copolymers, silicone, silicone-acrylic acid and other polyorganosiloxane rubber polymers. The core may contain only one of these substances, or may contain two or more of these substances.
[0057] On the other hand, the component constituting the shell only needs to contain a carboxyl group. For example, it may be a resin containing a carboxyl group. In addition, it may also be composed of a compound graft-polymerized on the component constituting the above core. Specific examples include carboxyl-containing vinyl monomers such as acrylic acid, methacrylic acid, crotonic acid, maleic acid, itaconic acid, fumaric acid, isocrotonic acid, salicylic acid, vinyloxyacetic acid, allyloxyacetic acid, 2-(meth)acryloyl propionic acid, 3-(meth)acryloyl butyric acid, and 4-vinyl benzoic acid.
[0058] Here, the amount of carboxyl groups present on the surface of the rubber particles is preferably 0.1 to 10 mmol / g, and more preferably 0.5 to 4 mmol / g. The amount of the carboxyl groups can be measured by FT-IR before and after the addition of the silane coupling agent having an amino group. Specifically, to the first resin composition (e.g., RKB-5810) in which the core-shell rubber having a carboxyl group is fully dispersed in the alicyclic epoxy resin, a silane coupling agent having an amino group (e.g., Z-6011) is gradually added, and the absorption peak derived from the carboxyl group (e.g., 1719 cm -1 ) is calculated by the amount added when the decrease of the amount of carboxyl groups converges. If the amount of carboxyl groups is within this range, it is easy to react with the amino compound of the silane compound described later.
[0059] The average particle size of the rubber particles can be as long as it is less than 300nm, preferably more than 10nm and less than 300nm, more preferably more than 20nm and less than 100nm, and particularly preferably more than 20nm and less than 60nm. The upper limit is further preferably 50nm. If the average particle size of the rubber particles is too small, it is difficult to disperse in the above-mentioned alicyclic epoxy compound. In addition, when the average particle size of the rubber particles is too small, the rubber particles as a whole are easily covered by the silane compound described later. If the rubber particles are covered with silane compounds, one rubber particle and multiple cellulose fibers are easily bonded via the silane compound. As a result, it is difficult for the cellulose fibers to move freely in the first resin composition, and the viscosity of the first resin composition sometimes becomes high. In contrast, if the average particle size of the rubber particles is more than 10nm, the rubber particles as a whole are not easily covered by the silane compound described later, which can reduce the viscosity of the first resin composition. On the other hand, if the average particle size of the rubber particles is less than 300nm, it is easy to configure multiple rubber particles around a cellulose fiber, which is easy to reduce the viscosity of the first resin composition. The above average particle size is a value measured based on JIS Z 8825. When there is a possibility of non-spherical shape or aggregation, it is desirable to directly observe / measure the particle size using a transmission electron microscope or the like to confirm whether it agrees with the above measurement result.
[0060] The core-shell rubber particles can be prepared by a known method. For example, the following methods can be used: a method of adding all the monomer components constituting the core and the shell at once and performing emulsion polymerization; a method of polymerizing a part of the monomer components to form the core and then continuously or intermittently adding the remaining part to form the shell; a method of continuously adding the monomer components from the beginning of polymerization; or a method of using masterbatch granulation, etc. It should be noted that the rubber particles can also be commercially available products.
[0061] In addition, the rubber particles may be those dispersed in advance in the alicyclic epoxy compound. For example, the rubber particles may be dispersed in the alicyclic epoxy compound or its polymer by a mixing and stirring device such as a high-speed mixer or a homogenizer. In addition, the rubber particles may be prepared in the alicyclic epoxy compound and used directly.
[0062] The amount of rubber particles in the first resin composition is appropriately selected according to the purpose, preferably more than 2% by mass and less than 20% by mass of the first resin composition (when the first resin composition contains volatile components, it is the non-volatile component of the first resin composition), more preferably more than 3% by mass and less than 5% by mass. In addition, according to the purpose of the first resin composition, the amount of rubber particles can also be more than 7% by mass and less than 9% by mass. In addition, the amount (mass) of rubber particles relative to the amount (mass) of the above-mentioned cellulose fibers can be appropriately selected according to the fiber diameter and fiber length of the cellulose fibers, preferably more than 0.1 times and less than 10 times, more preferably more than 0.2 times and less than 3 times. If the amount of rubber particles is more than 2% by mass of the first resin composition, it is easy to fully adhere to the surroundings of the cellulose fibers via the silane compound described later. On the other hand, if the amount of rubber particles is less than 20% by mass of the first resin composition, the rubber particles in the first resin composition are not easy to be free, and the viscosity of the first resin composition easily falls within the desired range.
[0063] Silane compounds
[0064] The silane compound is a compound containing an amino group and silicon (Si), and any compound can be used as long as the rubber particles and the cellulose fibers can be bonded via the silane compound. Examples of the silane compound include silane coupling agents having an amino group (hereinafter also referred to as "aminosilane coupling agents").
[0065] Examples of aminosilane coupling agents include 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, 3-triethoxysilyl-N-(1,3-dimethylbutylene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, etc. The first resin composition may contain only one of these substances, or may contain two or more of these substances. Among them, 3-aminopropyltriethoxysilane is preferred from the viewpoint of being easy to obtain and making the distance between cellulose fibers and rubber particles fall into an appropriate range.
[0066] The amount (mass) of the silane compound in the first resin composition is appropriately selected according to the purpose, and is preferably 0.1 times or more and 0.5 times or less, more preferably 0.2 times or more and 0.4 times or less, and further preferably 0.25 times or more and 0.35 times or less relative to the amount (mass) of the above-mentioned rubber particles. As described above, it is preferred that the surroundings of the above-mentioned rubber particles are not completely covered by the silane compound. Therefore, the amount of the silane compound is preferably 0.5 times or less of the amount of the rubber particles. On the other hand, in order to configure the rubber particles around the cellulose fibers, it is preferred that the amount of the silane compound is 0.1 times or more of the amount of the rubber particles. In addition, in particular, if the above-mentioned ratio is 0.25 times or more and 0.35 times or less, the toughness of the obtained cured resin composition becomes good, and the viscosity of the first resin composition becomes low.
[0067] ·other
[0068] In addition to the alicyclic epoxy compound, cellulose fiber, rubber particles and silane compound, other components may be included within the range not impairing the purpose and effect of the present invention. Examples of other components include solvents, various additives, resins other than the alicyclic epoxy compound, and the like.
[0069] ·Viscosity of the first resin composition
[0070] The viscosity of the first resin composition can be appropriately selected according to its use. For the first resin composition without a curing agent, the value measured by a cone-plate viscometer at 25°C, 5 rpm, and 30 seconds is preferably 0.1 Pa·s or more and 300 Pa·s or less, and more preferably 0.5 Pa·s or more and 100 Pa·s or less. If the viscosity of the first resin composition is within this range, the operability when the first resin composition is mixed with other compositions or when only the first resin composition is cured to form a composite material becomes good.
[0071] 2. Preparation method of the first resin composition
[0072] The method for preparing the first resin composition is not particularly limited, but the following method is preferred from the viewpoint of arranging the rubber particles around the cellulose fibers via the silane compound as described above.
[0073] First, a process of mixing alicyclic epoxy resin, rubber particles and silane compounds is performed. There is no particular limitation on the mixing method, and for example, stirring using a known mixer may be used. If they are mixed, the carboxyl group of the rubber particles reacts with the amine of the silane compound to form a bonded state. Next, a process of mixing cellulose fibers in the composition is performed. There is no particular limitation on the mixing method, but from the perspective of uniformly dispersing the cellulose fibers in the first resin composition and bonding the rubber particles around the cellulose fibers via the silane compound, it is preferred to use a three-roll mill or the like for mixing. Usually, after mixing, heating is also performed in the process of defoaming the bubbles during mixing, but in the present invention, since mixing is performed in a state containing cellulose fibers, it is ideal to remove moisture absorbed during mixing and moisture generated during the reaction. Defoaming after mixing is preferably performed by vacuum defoaming after heating or while heating.
[0074] 3. Curing the resin composition
[0075] In this specification, the state in which the first resin composition (alicyclic epoxy compound) is cured by a curing agent is referred to as a cured resin composition, and the state including the first resin composition and the curing agent, that is, the state before curing is referred to as a curing agent-containing resin composition.
[0076] The first resin composition is mixed with various curing agents, and the alicyclic epoxy compound is reacted to obtain a cured resin composition. The curing agent may be a compound known as a curing agent for epoxy resin. The reaction of the alicyclic epoxy compound can be roughly divided into the following three types.
[0077] (i) Co-condensation reaction of epoxy group and acid anhydride group.
[0078] (ii) The epoxy group is self-polymerized by a basic catalyst or an acidic catalyst.
[0079] (iii) Addition reaction of epoxy groups with active hydrogen compounds.
[0080] Hereinafter, each of the above reactions will be described.
[0081] (i) Co-condensation reaction of epoxy group and anhydride group
[0082] Examples of the acid anhydride used when subjecting the epoxy group to a polycondensation reaction with the acid anhydride group include phthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, hexahydrophthalic anhydride, tetrahydrophthalic anhydride, trialkyltetrahydrophthalic anhydride, methylnadic anhydride, methylcyclohexenedicarboxylic anhydride, trimellitic anhydride, pyromellitic anhydride, benzophenonetetracarboxylic anhydride, ethylene glycol ditrimellitate, glycerol trimellitate, dodecenylsuccinic anhydride, polyazelaic anhydride, poly(ethyloctadecane diacid) anhydride, and the like.
[0083] It is desirable that the usage amount of the curing agent when carrying out the above-mentioned reaction is relative to the epoxy equivalent of the first resin combination, so that anhydride equivalent and OH equivalent are consistent.But, in the case of using anhydrides as curing agent, the best equivalent ratio of the kind of known each kind of anhydride, each kind of desired physical property (heat deformation temperature, weight loss rate, dielectric constant, PCT moisture absorption rate) is different, preferably with reference to manufacturer recommended value.For example, relative to the amount 100 mass parts of the compound with epoxy group in the first resin combination, the amount of anhydride is preferably more than 50 mass parts and less than 400 mass parts, more preferably more than 70 mass parts and less than 200 mass parts.
[0084] In the above reaction, a catalyst may be used. Examples of the catalyst include: urea compounds such as 3-(3,4-dichlorophenyl)-1,1-dimethylurea; imidazole compounds such as 2-methylimidazole and 2-ethyl-4-methylimidazole; adducts of imidazole compounds and epoxy resins; organic phosphorus compounds such as triphenylphosphine; boric acid esters such as tetraphenylphosphine tetraphenylborate; diazabicycloundecene; phosphonium salts such as tetraalkylphosphonium salts, tetraphenylphosphonium salts, and alkyltriphenylphosphonium salts; and the like.
[0085] The amount of the catalyst used is preferably 0.1 to 10 parts by mass, more preferably 0.5 to 5 parts by mass, based on 100 parts by mass of the compound having an epoxy group (eg, alicyclic epoxy compound) in the first resin composition.
[0086] (ii) Epoxy groups self-polymerize with a basic catalyst or an acidic catalyst
[0087] The basic catalyst or acidic catalyst can be used as long as it can cause the compound having an epoxy group (e.g., alicyclic epoxy compound) in the first resin composition to self-polymerize. Examples thereof include cationic curing catalysts. Examples of cationic curing catalysts include photocationic polymerization initiators and thermal cationic polymerization initiators. These cationic curing catalysts can be used alone or in combination of two or more.
[0088] Examples of the photocationic polymerization initiator include sulfonium salts such as triarylsulfonium hexafluorophosphate and triarylsulfonium hexafluoroantimonate; iodonium salts such as diaryliodonium hexafluorophosphate, diphenyliodonium hexafluoroantimonate, bis(dodecylbenzene)iodonium tetrakis(pentafluorophenyl)borate, and iodonium [4-(4-methylphenyl-2-methylpropyl)phenyl] hexafluorophosphate ((4-Methylphenyl) [4-(2-methylpropyl)phenyl]iodonium hexafluorophosphate); phosphonium salts such as tetrafluorophosphonium hexafluorophosphate; pyridinium salts, etc.
[0089] Examples of thermal cationic polymerization initiators include aryl diazonium salts, aryl iodonium salts, aryl sulfonium salts, allene-ion complexes, etc. In addition, chelate compounds of metals such as aluminum and titanium with acetoacetic acid or diketones and compounds of silanols such as triphenylsilanol; or chelate compounds of metals such as aluminum and titanium with acetoacetic acid or diketones and compounds of phenols such as bisphenol S, etc. can also be used.
[0090] The amount of the cationic curing catalyst used is not particularly limited, but is preferably 0.01 to 30 parts by weight, more preferably about 0.05 to 10 parts by weight, based on 100 parts by weight of the total amount of the compound having an epoxy group in the first resin composition.
[0091] In addition, when a photocationic polymerization initiator is used, a photosensitizer can be used in combination. A photosensitizer is a substance that further enhances the effect of the above-mentioned photocationic polymerization initiator and further promotes the photocationic polymerization of the above-mentioned alicyclic epoxy compounds and the like. Such photosensitizers are not particularly limited, and for example, carbonyl compounds, organic sulfur compounds, persulfides, redox compounds, azo compounds, diazo compounds, halogen compounds, photoreductive pigments, etc. can be used. Specific examples of photosensitizers include: benzoin derivatives such as benzoin methyl ether and benzoin isopropyl ether; benzophenone derivatives such as benzophenone, 2,4-dichlorobenzophenone, methyl o-benzoylbenzoate, and 4,4'-bis(dimethylamino)benzophenone; thioxanthone derivatives such as 2-chlorothioxanthone and 2-isopropylthioxanthone; anthraquinone derivatives such as 2-chloroanthraquinone and 2-methylanthraquinone; anthraquinone derivatives such as dipropoxyanthracene and dibutoxyanthracene, etc. These photosensitizers can be used alone or in combination of two or more.
[0092] (iii) Addition reaction of epoxy groups with active hydrogen compounds
[0093] When the compound having an epoxy group (e.g., an alicyclic epoxy compound) in the first resin composition is subjected to an addition reaction with an active hydrogen compound, 1) an active hydrogen compound (B1) having a pKa of 10 or less may be used as the active hydrogen compound. In addition, 2) an active hydrogen compound (B2) having a pKa of more than 10 may be used as the active hydrogen compound, and a cationic catalyst (C1) may be used to cause the compound having an epoxy group to undergo an addition reaction with the active hydrogen compound. Furthermore, 3) an active hydrogen compound (B2) having a pKa of more than 10 may be used as the active hydrogen compound, and a catalyst (C2) that generates a cation by reaction or light irradiation may be used to cause the compound having an epoxy group to undergo an addition reaction with the active hydrogen compound.
[0094] About 1)
[0095] When an active hydrogen compound (B1) having a pKa of 10 or less is used as the active hydrogen compound, the pKa of the active hydrogen compound (B1) may be 10 or less, and is preferably 6 to 10. An active hydrogen compound having such a low pKa easily releases H + Therefore, even in the absence of a catalyst, alicyclic epoxy compounds and the like can be cured.
[0096] In this application specification, pKa is the acid dissociation equilibrium constant, which is defined as pKa = -logKa, Ka = [H3O + ][B - ] / [BH](BH: organic acid, B - : conjugate base of an organic acid). It should be noted that, when one molecule of the curing agent contains two or more acidic groups, pKa refers to the first dissociation constant pKa1.
[0097] The acid dissociation constant (pKa) of an active hydrogen compound varies depending on the structure of the active hydrogen compound. That is, the pKa of a compound in which a functional group having active hydrogen is directly bonded to an aromatic group (aromatic ring) is lower than the pKa of a compound in which a functional group having active hydrogen is directly bonded to an aliphatic group. In addition, the pKa decreases in the order of thiol < alcohol < amine.
[0098] In addition, the acid dissociation constant (pKa) also varies according to the type of solvent around the active hydrogen compound. In this specification, in order to distinguish active hydrogen compounds (B1) from active hydrogen compounds (B2), pKa in water is used as an index. pKa can be measured using a pH meter, for example, to determine the hydrogen ion concentration in water, calculated from the concentration of the substance and the hydrogen ion concentration. Alternatively, the pKa is used in the case where the value of pKa is known in the literature (e.g., pKa Data Compiled by R. Williams, https: / / organicchemistrydata.org / hansreich / resources / pka / pka_data / pka-compi lation-williams.pdf), and in the case where the value of pKa is not known in the literature, the active hydrogen compound can be described by a structural formula, and the pKa value of the compound having more than 2 carbon atoms starting from the carbon atom bonded to the functional group having active hydrogen (equivalent to the compound having more than 2 carbon atoms starting from the carbon atom bonded to the functional group having active hydrogen) is used.
[0099] In the case of a water-insoluble active hydrogen compound, the pKa value can be estimated from the structure around the functional group that becomes active hydrogen. For example, the pKa value of 4,4'-thiobisbenzenethiol can be the pKa value of benzenethiol.
[0100] Examples of the active hydrogen compound (B1) having a pKa of 10 or less include thiol compounds having a pKa of 10 or less and bisphenol compounds having a pKa of 10 or less. The bisphenol compound may be a compound having an active hydrogen functional group such as thiol or alcohol directly bonded to a conjugated structure such as a benzene ring. In this way, the curing agent having a conjugated structure bonded to an active hydrogen functional group is in a stabilized conjugated base state and therefore easily releases hydrogen ions.
[0101] Bisphenol compounds having a pKa of 10 or less are compounds having two phenolic hydroxyl groups in one molecule, and examples thereof include bisphenols such as 2,2-bis(4-hydroxyphenyl)propane (bisphenol A), 1,1-bis(4-hydroxyphenyl)ethane (bisphenol AD), bis(hydroxyphenyl)methane (bisphenol F), bisphenol fluorene, and biscresol fluorene.
[0102] The thiol compound having a pKa of 10 or less may be any compound having two or more thiol groups in one molecule and having a pKa satisfying the above range, and is preferably a thiol compound containing an aromatic ring (aromatic thiol compound). The number of aromatic rings contained in one molecule of the aromatic thiol compound may be at least 1, preferably 1 to 3, and more preferably 1 to 2.
[0103] Examples of the aromatic thiol compounds include 1,2-dimercaptobenzene, 1,3-dimercaptobenzene, 1,4-dimercaptobenzene, 1,2-bis(mercaptomethyl)benzene, 1,3-bis(mercaptomethyl)benzene, 1,4-bis(mercaptomethyl)benzene, 1,3-bis(mercaptoethyl)benzene, 1,4-bis(mercaptoethyl)benzene, 1,2-bis(mercaptomethoxy)benzene, 1,3-bis(mercaptomethoxy)benzene, 1,4-bis(mercaptomethoxy)benzene, 1,2-bis(mercaptoethoxy)benzene, 1,3-bis(mercaptoethoxy)benzene, 1,4-bis(mercaptoethoxy)benzene, 1,2,3-trimercaptobenzene, and 1,2,4-trimercaptobenzene. , 1,3,5-trimercaptobenzene, 1,2,3-tris(mercaptomethyl)benzene, 1,2,4-tris(mercaptomethyl)benzene, 1,3,5-tris(mercaptomethyl)benzene, 1,2,3-tris(mercaptoethyl)benzene, 1,2,4-tris(mercaptoethyl)benzene, 1,3,5-tris(mercaptoethyl)benzene, 1,2,3-tris(mercaptomethoxy)benzene, 1,2,4-tris(mercaptomethoxy)benzene, 1,3,5-tris(mercaptomethoxy)benzene, 1,2,3-tris(mercaptoethoxy)benzene, 1,2,4-tris(mercaptoethoxy)benzene, 1,3,5-tris(mercaptoethoxy)benzene, 1,2,3,4-tetramercaptobenzene, 1,2,3, 5-Tetramercaptobenzene, 1,2,4,5-Tetramercaptobenzene, 1,2,3,4-Tetrakis(mercaptomethyl)benzene, 1,2,3,5-Tetrakis(mercaptomethyl)benzene, 1,2,4,5-Tetrakis(mercaptomethyl)benzene, 1,2,3,4-Tetrakis(mercaptoethyl)benzene, 1,2,3,5-Tetrakis(mercaptoethyl)benzene, 1,2,4,5-Tetrakis(mercaptoethyl)benzene, 1,2,3,4-Tetrakis(mercaptoethyl)benzene, 1,2,3,5-Tetrakis(mercaptomethoxy)benzene, 1,2,4,5-Tetrakis(mercaptomethoxy)benzene, 1,2,3,4-Tetrakis(mercaptoethoxy)benzene, 1,2,3,5-Tetrakis(mercaptoethoxy)benzene, 1,2,4, 5-Tetrakis(mercaptoethoxy)benzene, 2,2'-dimercaptobiphenyl, 4,4'-dimercaptobiphenyl, 4,4'-dimercaptobibenzyl, 2,5-toluenedithiol, 3,4-toluenedithiol, 1,4-naphthalenedithiol, 1,5-naphthalenedithiol, 2,6-naphthalenedithiol, 2,7-naphthalenedithiol, 2,4-dimethylbenzene-1,3-dithiol, 4,5-dimethylbenzene-1,3-dithiol, 9,10-anthracene dimethylthiol, 1,3-bis(p-methoxyphenyl)propane-2,2-dithiol, 1,3-diphenylpropane-2,2-dithiol, phenylmethane-1,1-dithiol, 2,4-bis(p-mercaptophenyl)pentane, etc.
[0104] The aromatic thiol compound may contain a sulfur atom in addition to the thiol group. Examples of such aromatic thiol compounds include 1,2-bis(mercaptomethylthio)benzene, 1,3-bis(mercaptomethylthio)benzene, 1,4-bis(mercaptomethylthio)benzene, 1,2-bis(mercaptoethylthio)benzene, 1,3-bis(mercaptoethylthio)benzene, 1,4-bis(mercaptoethylthio)benzene, 1,2,3-tris(mercaptomethylthio)benzene, 1,2,4-tris(mercaptomethylthio)benzene, 1,3,5-tris(mercaptomethylthio)benzene, 1,2,3-tris(mercaptoethylthio)benzene, 1,2 ,4-tris(mercaptoethylthio)benzene, 1,3,5-tris(mercaptoethylthio)benzene, 1,2,3,4-tetrakis(mercaptomethylthio)benzene, 1,2,3,5-tetrakis(mercaptomethylthio)benzene, 1,2,4,5-tetrakis(mercaptomethylthio)benzene, 1,2,3,4-tetrakis(mercaptoethylthio)benzene, 1,2,3,5-tetrakis(mercaptoethylthio)benzene, 1,2,4,5-tetrakis(mercaptoethylthio)benzene, 1,3,5-triazine-2,4,6-trithiol (thiocyanuric acid), 4,4'-thiobisbenzenethiol, etc. These may be used alone or in combination of two or more.
[0105] The thiol equivalent of the thiol compound having a pKa of 10 or less is not particularly limited, and is, for example, 300 g / eq or less, preferably 150 g / eq or less. If the thiol equivalent is within this range, the curing reactivity of the resin composition containing the curing agent and the refractive index of the obtained cured resin composition can be easily further improved.
[0106] The number of thiol groups (functional group number) contained in one molecule of the thiol compound having a pKa of 10 or less is preferably 2 to 10, more preferably 2 to 4, and more preferably 3. When the number of thiol groups is within this range, the curing reactivity of the resin composition containing the curing agent and the refractive index of the obtained cured resin composition can be easily further improved.
[0107] The weight average molecular weight of the thiol compound having a pKa of 10 or less is not particularly limited, but is preferably 100 to 10000, and more preferably 100 to 1000. The weight average molecular weight can be measured by GPC in terms of polystyrene.
[0108] Among them, the active hydrogen compound (B1) having a pKa of 10 or less preferably includes a thiol compound having a pKa of 10 or less, and more preferably includes a thiol compound having a pKa of 7 or less.
[0109] The amount of the active hydrogen compound (B1) having a pKa of 10 or less is preferably 15 to 400 parts by mass relative to the total amount of 100 parts by mass of the compound containing an epoxy group in the first resin composition. If the amount of the active hydrogen compound (B1) is 15 parts by mass or more, it is easier to activate the alicyclic epoxy compound and the like, and it is easy to obtain sufficient curing reactivity. If the amount of the active hydrogen compound (B1) is 400 parts by mass or less, it is easy to suppress the viscosity increase of the resin composition containing the curing agent, and therefore it is less likely to damage the operability. From the same viewpoint, the amount of the active hydrogen compound (B1) is more preferably 30 to 200 parts by mass relative to the total amount of 100 parts by mass of the compound containing an epoxy group.
[0110] About 2)
[0111] In the case of 2) above, an active hydrogen compound (B2) having a pKa exceeding 10 and a cationic catalyst (C1) are used as components for curing the alicyclic epoxy compound.
[0112] (Active hydrogen compound (B2))
[0113] The pKa of the active hydrogen compound (B2) in 2) is higher than 10, preferably 10 to 14. Since an active hydrogen compound having such a high pKa is difficult to release H + Therefore, it is difficult to activate alicyclic epoxy compounds when used alone. Therefore, H + The cationic catalyst (C1) can cure alicyclic epoxy compounds and the like.
[0114] The active hydrogen compound (B2) having a pKa of more than 10 preferably includes an amine compound having a pKa of more than 10 or a thiol compound having a pKa of more than 10.
[0115] The amine compound having a pKa exceeding 10 may be any compound having two or more amino groups in one molecule and having a pKa satisfying the above range, preferably being 11 or more, and more preferably being 15 or more, and preferably includes an amine compound containing an aromatic ring (aromatic amine compound). Examples of aromatic amine compounds include 4,4'-diaminodiphenyl sulfide (manufactured by Seika Co., Ltd., ASD) and 4,4'-diaminodiphenyl sulfone (manufactured by Seika Co., Ltd., Seika Cure S).
[0116] The thiol compound having a pKa exceeding 10 may be any compound having two or more thiol groups in one molecule and having a pKa satisfying the above range, and is preferably a thiol compound not containing an aromatic ring (aliphatic thiol compound). The aliphatic thiol compound may be an aliphatic thiol compound having an ester bond in the molecule or an aliphatic thiol compound not having an ester bond in the molecule.
[0117] Examples of the aliphatic thiol compound having an ester bond in the molecule include trimethylolpropane tris(3-mercaptopropionate) (manufactured by SC Organic Chemicals, TMMP), tris-[(3-mercaptopropionyloxy)-ethyl]-isocyanurate (manufactured by SC Organic Chemicals, TEMPIC), pentaerythritol tetrakis(3-mercaptopropionate) (manufactured by SC Organic Chemicals, PEMP), tetraethylene glycol bis(3-mercaptopropionate) (manufactured by SC Organic Chemicals, EGMP-4), dipentaerythritol hexa(3-mercaptopropionate) (manufactured by SC Organic Chemicals, DPMP), pentaerythritol tetrakis(3-mercaptobutyrate) (manufactured by Showa Denko K.K., Karenz MT (registered trademark) PE1), 1,3,5-tris(3-mercaptobutyryloxyethyl)-1,3,5-triazine-2,4,6,(1H,3H,5H)-trione (manufactured by Showa Denko K.K., Karenz MT (registered trademark) NR1), 1,4-bis(3-mercaptobutyryloxy)butane (manufactured by Showa Denko K.K., Karenz MT (registered trademark) BD1), and the like.
[0118] Examples of the aliphatic thiol-based compound having no ester bond in the molecule include compounds represented by the following formula (1) or (2).
[0119] [Chemical formula 4]
[0120]
[0121] In formula (1), R 1 and R 2 Each R is independently selected from the group consisting of a hydrogen atom or an alkyl group having 1 to 12 carbon atoms. 3 , R 4 , R 5 and R 6 Each is independently selected from the group consisting of mercaptomethyl, mercaptoethyl and mercaptopropyl.
[0122] Examples of the compound represented by formula (1) include 1,3,4,6-tetrakis(2-mercaptoethyl)glycoluril (manufactured by Shikoku Chemical Industry Co., Ltd., TS-G), (1,3,4,6-tetrakis(3-mercaptopropyl)glycoluril (manufactured by Shikoku Chemical Industry Co., Ltd., C3 TS-G), 1,3,4,6-tetrakis(mercaptomethyl)glycoluril, 1,3,4,6-tetrakis(mercaptomethyl)-3a-methylglycoluril, 1,3,4,6-tetrakis(2-mercaptoethyl)-3a-methylglycoluril, 1,3,4,6-tetrakis(3-mercaptopropyl)-3a-methylglycoluril, 1,3,4,6-tetrakis(mercaptomethyl)-3a,6a-dimethylglycoluril, 1,3,4,6-tetrakis(2-mercaptoethyl)-3a,6a-dimethylglycoluril, 1,3,4,6-tetrakis(3-mercaptopropyl)-3a,6a-dimethylglycoluril, etc. Among them, 1,3,4,6-tetrakis(2-mercaptoethyl)glycoluril and 1,3,4,6-tetrakis(3-mercaptopropyl)glycoluril are particularly preferred.
[0123] [Chemical formula 5]
[0124] (R 8 ) m -A-(R 7 -SH) n (2)
[0125] In formula (2), A is a residue of a polyol having n+m hydroxyl groups.
[0126] R 7 Each of the groups is independently an alkylene group having 1 to 10 carbon atoms.
[0127] R 8 Each of the groups is independently a hydrogen atom or an alkyl group having 1 to 10 carbon atoms.
[0128] m is an integer greater than or equal to 0.
[0129] n is an integer of 3 or more.
[0130] Examples of the compound represented by formula (2) include pentaerythritol tripropyl mercaptan (manufactured by SC Organic Chemicals Co., Ltd., Multhiol Y-3), pentaerythritol tetrapropyl mercaptan, etc. Among them, pentaerythritol tripropyl mercaptan is particularly preferred.
[0131] Furthermore, as the aliphatic thiol compound having no ester bond in the molecule, a trifunctional or higher functional polythiol compound having two or more thioether bonds in the molecule may be used. Examples of such thiol compounds include 1,2,3-tris(mercaptomethylthio)propane, 1,2,3-tris(2-mercaptoethylthio)propane, 1,2,3-tris(3-mercaptopropylthio)propane, 4-mercaptomethyl-1,8-dimercapto-3,6-dithiooctane, 5,7-dimercaptomethyl-1,11-dimercapto-3,6,9-trithioundecane, 4,7-dimercaptomethyl-1,11-dimercapto-3,6,9-trithioundecane, 4,8-dimercaptomethyl-1,11-dimercapto-3,6,9-trithioundecane, tetrakis(mercaptomethylthiomethyl)methane, tetrakis(2-mercaptoethylthiomethyl)methane, and tetrakis(3-mercaptopropylthiomethyl)methane. , 1,1,3,3-tetrakis(mercaptomethylthio)propane, 1,1,2,2-tetrakis(mercaptomethylthio)ethane, 1,1,5,5-tetrakis(mercaptomethylthio)-3-thiopentane, 1,1,6,6-tetrakis(mercaptomethylthio)-3,4-dithiohexane, 2,2-bis(mercaptomethylthio)ethanethiol, 3-mercaptomethylthio-1,7-dimercapto-2,6-dithioheptane, 3,6-bis(mercaptomethylthio)-1,9-dimercapto-2,5,8-trithiononane, 3-mercaptomethylthio-1,6-dimercapto-2,5-dithiohexane, 1,1,9,9-tetrakis(mercaptomethylthio)-5-(3,3-bis(mercaptomethylthio)-1-thiopropyl)3,7- Nonane disulfide, tris(2,2-bis(mercaptomethylthio)ethyl)methane, tris(4,4-bis(mercaptomethylthio)-2-thiobutyl)methane, tetrakis(2,2-bis(mercaptomethylthio)ethyl)methane, tetrakis(4,4-bis(mercaptomethylthio)-2-thiobutyl)methane, 3,5,9,11-tetrakis(mercaptomethylthio)-1,13-dimercapto-2,6,8,12-tetrathiotridecane, 3,5,9,11,15,17-hexa(mercaptomethylthio)-1,19-dimercapto-2,6,8,12,14,18-hexathiononadecane, 9-(2,2-bis(mercaptomethylthio)ethyl)-3,5,13,15-tetrakis(mercaptomethylthio)-1,17 -dimercapto-2,6,8,10,12,16-hexathioheptadecane, 3,4,8,9-tetrakis(mercaptomethylthio)-1,11-dimercapto-2,5,7,10-tetrathioundecane, 3,4,8,9,13,14-hexa(mercaptomethylthio)-1,16-dimercapto-2,5,7,10,12,15-hexathiohexadecane, 8-[bis(mercaptomethylthio)methyl]-3,4,12,13-tetrakis(mercaptomethylthio)-1,15-dimercapto-2,5,7,9,11,14-hexathiopentadecane, 4,6-bis[3,5-bis(mercaptomethylthio)-7-mercapto-2,6-dithioheptylthio]-1,3-dithiane, 4-[3,5-bis(mercaptomethylthio)-7-mercapto-2,6-dithioheptylthio]-6-mercaptomethylthio-1,3-dithiane, 1,1-bis[4-(6-mercaptomethylthio)-1,3-dithianylthio]-1,3-bis(mercaptomethylthio)propane, 1-[4-(6-mercaptomethylthio)-1,3-dithianylthio]-3-[2,2-bis(mercaptomethylthio)ethyl]-7,9-bis(mercaptomethylthio)-2,4,6,10-tetrathiaundecane, 3-[2-(1,3-dithiocyclobutyl)]methyl-7,9-bis(mercaptomethylthio)-1,11-dimercapto-2,4,6,10-tetrathiaundecane, 9-[2-(1,3-dithiocyclobutyl)]methyl-3 ,5,13,15-tetrakis(mercaptomethylthio)-1,17-dimercapto-2,6,8,10,12,16-hexathioheptadecane, 3-[2-(1,3-dithiocyclobutyl)]methyl-7,9,13,15-tetrakis(mercaptomethylthio)-1,17-dimercapto-2,4,6,10,12,16-hexathioheptadecane and other acyclic polythiol compounds; 4,6-bis[4-(6-mercaptomethylthio)-1,3-dithianylthio]-6-[4-(6-mercaptomethylthio)-1,3-dithianylthio]-1,3-dithiane, 4-[3,4,8,9-tetrakis(mercaptomethylthio)-11-mercapto-2,5,7,10-tetrathioundecyl]-5-mercaptomethyl Thio-1,3-dithiolane, 4,5-bis[3,4-bis(mercaptomethylthio)-6-mercapto-2,5-dithiohexylthio]-1,3-dithiolane, 4-[3,4-bis(mercaptomethylthio)-6-mercapto-2,5-dithiohexylthio]-5-mercaptomethylthio-1,3-dithiolane, 4-[3-bis(mercaptomethylthio)methyl-5,6-bis(mercaptomethylthio)-8-mercapto-2,4,7-trithiooctyl]-5-mercaptomethylthio-1,3-dithiolane, 2-{bis[3,4-bis(mercaptomethylthio)-6-mercapto-2,5-dithiohexylthio]methyl}-1,3-dithiocyclobutane, 2-[3,4-bis(mercaptomethylthio)-6-mercapto-2, Polythiol compounds having a ring structure such as 5-dithiohexylthio]mercaptomethylthiomethyl-1,3-dithiocyclobutane, 2-[3,4,8,9-tetrakis(mercaptomethylthio)-11-mercapto-2,5,7,10-tetrathioundecylthiol]mercaptomethylthiomethyl-1,3-dithiocyclobutane, 2-[3-bis(mercaptomethylthio)methyl-5,6-bis(mercaptomethylthio)-8-mercapto-2,4,7-trithiooctyl]mercaptomethylthiomethyl-1,3-dithiocyclobutane, and 4-{1-[2-(1,3-dithiocyclobutyl)]-3-mercapto-2-thiopropylthio}-5-[1,2-bis(mercaptomethylthio)-4-mercapto-3-thiobutylthio]-1,3-dithiolane.
[0132] The thiol equivalent of the thiol compound having a pKa exceeding 10 is not particularly limited, and is, for example, 90 to 150 g / eq, preferably 90 to 140 g / eq. When the thiol equivalent is within this range, the curing reactivity of the resin composition containing the curing agent is easily further improved, and the refractive index, flexural modulus, etc. of the obtained cured resin composition are also easily further improved.
[0133] The number of thiol groups (functional group number) contained in one molecule of the thiol compound having a pKa of more than 10 is preferably 2 to 4, more preferably 3 to 4, and even more preferably 4. When the number of thiol groups is equal to or greater than the lower limit, the curing reactivity of the resin composition containing the curing agent is likely to be further improved, and the refractive index, bending modulus, etc. of the cured resin composition are also likely to be further improved. In addition, when the number of thiol groups is 4 or less, the number of thiol groups remaining without reaction can be further reduced, and the reduction in physical properties can be suppressed.
[0134] The weight average molecular weight of the thiol compound having a pKa exceeding 10 is not particularly limited, but is preferably 100 to 10000, and more preferably 100 to 1000. The weight average molecular weight can be measured by the same method as described above.
[0135] The amount of the active hydrogen compound (B2) having a pKa greater than 10 is preferably 40 to 200 parts by mass relative to 100 parts by mass of the total amount of the resin containing the epoxy group (preferably the total amount of the alicyclic epoxy resin). If the amount of the active hydrogen compound (B2) is 40 parts by mass or more, it is easier to activate the alicyclic epoxy compound and to improve the curing reactivity. If the amount of the active hydrogen compound (B2) is 200 parts by mass or less, the viscosity increase of the resin composition containing the curing agent can be suppressed, and the handling property is not easily impaired. From the same point of view, the amount of the active hydrogen compound (B2) is more preferably 50 to 150 parts by mass relative to 100 parts by mass of the total amount of the resin containing the epoxy group (preferably the total amount of the alicyclic epoxy resin).
[0136] (Cationic Catalyst (C1))
[0137] Cationic catalyst (C1) is a catalyst that promotes H +The released compound is a compound that does not promote the self-polymerization of the compound monomer having an epoxy group but promotes the reaction of the compound having an epoxy group with an active hydrogen compound. The so-called non-promotion of self-polymerization can be confirmed by the fact that the mixture consisting only of the compound having an epoxy group and the catalyst does not generate heat (curing) due to heat. In the self-polymerization reaction, two epoxy groups react with respect to one epoxy group, that is, in the alicyclic epoxy compound having two epoxy groups, each molecule reacts with four epoxy groups, so the degree of crosslinking is easily increased and the toughness is easily reduced. In contrast, the cationic catalyst (C1) does not undergo such a self-polymerization reaction, and plays the role of promoting the activation of the epoxy group and the activation of the active hydrogen compound. By directly adding a cationic catalyst (C1), the reaction can be carried out rapidly. Therefore, in an environment where heating is not possible, such as in cold areas, and in the case of wanting to suppress the heating / light irradiation energy required for the generation of cationic catalysts such as catalysts (C2), it can also be used as a catalyst for a two-component resin composition containing a curing agent.
[0138] Activation of epoxy groups refers to interaction with the oxygen of epoxy groups to facilitate nucleophilic attack of the carbon of epoxy groups. Compounds that can interact with the oxygen of epoxy groups include positively charged compounds. As a reaction mechanism, the oxygen atom of epoxy groups interacts with the positively charged catalyst, making the carbon atom of epoxy groups slightly positively charged, thereby promoting nucleophilic attack of active hydrides. Activation of active hydrogen compounds refers to the extraction of hydrogen from active hydrogen compounds.
[0139] Therefore, the cationic catalyst (C1) is a base used when curing a compound having an epoxy group, and is preferably a compound that maintains a positive charge after abstracting hydrogen and has a steric structure capable of interacting with oxygen of the epoxy group.
[0140] Such a cationic catalyst (C1) is preferably an amine. Examples of the amine include ammonium salts, amines having an amidine structure, and amines having a guanidine structure.
[0141] Examples of the ammonium salt include triethylmethylammonium 2-ethylhexane salt (product name: U-CAT 18X, manufactured by SAN-APRO Co., Ltd.).
[0142] Examples of the amines having an amidine structure include diazabicycloundecene (DBU) and diazabicyclononene (DBN), and examples of salts of the amines include 2-ethylhexanoate of DBU (product name: SA1, manufactured by SAN-APRO).
[0143] Examples of amines having a guanidine structure (including guanidine groups) include tetramethylguanidine, and examples of butyltriphenylborate include 1,2-dicyclohexyl-4,4,5,5-tetramethylbiguanidine n-butyltriphenylborate (product name: WPGK-300 (FUJIFILM Wako)).
[0144] Among them, amines having an amidine structure or salts thereof, and amines having a guanidine structure or salts thereof are preferred, and amines having a guanidine structure or salts thereof are more preferred.
[0145] The amount of the cationic catalyst (C1) used is preferably 1 to 10 parts by mass relative to 100 parts by mass of the total amount of the compound containing an epoxy group. If the amount of the cationic catalyst (C1) used is 1 part by mass or more, it is easier to activate the alicyclic epoxy compound and the like, and it is easy to obtain sufficient curing reactivity. When the amount of the cationic catalyst (C1) used is 10 parts by mass or less, after adding the catalyst, the time that can be used without curing (referred to as the usable time) can be further extended. In addition, the reduction in physical properties such as the glass transition temperature and elastic modulus caused by excessive residue of the catalyst in the curing resin composition can be further suppressed. From the same viewpoint, the amount of the cationic catalyst (C1) used is more preferably 1 to 5 parts by mass relative to 100 parts by mass of the total amount of the compound containing an epoxy group.
[0146] About 3)
[0147] In the case of 3) above, as components for curing the compound having an epoxy group, an active hydrogen compound (B2) having a pKa exceeding 10 and a catalyst (C2) that generates cations by reaction or light irradiation are used.
[0148] As mentioned above, active hydrogen compounds with high pKa are difficult to release H + Therefore, it is difficult to activate alicyclic epoxy compounds when used alone. Therefore, by further combining, H + The catalyst (C2) can improve the curing reactivity of alicyclic epoxy compounds and the like. In addition, since the curing timing can be adjusted by the timing of the reaction and light irradiation, it is easy to take into account the storage stability. In addition, the curing agent-containing resin composition containing the catalyst (C2) has fluidity even when stored at, for example, 40°C / 24 hours, and has excellent storage stability. Therefore, the catalyst (C2) is particularly suitable as a catalyst for a one-liquid curing agent-containing resin composition.
[0149] (Active hydrogen compound with pKa exceeding 10 (B2))
[0150] The active hydrogen compound (B2) having a pKa of more than 10 can be the same as those described above, and can be selected according to the type of catalyst (C2). For example, when the catalyst (C2) is dicyandiamide, the active hydrogen compound (B2) is preferably an active hydrogen compound that reacts with dicyandiamide to form guanidine (reaction accelerator).
[0151] When the active hydrogen compound (B2) is a thiol compound, dicyandiamide reacts as follows by heating to produce guanidine.
[0152] [Chemical formula 6]
[0153]
[0154] The generated guanidine further reacts with a thiol compound to form a guanidinium ion, thereby promoting the ring-opening of the alicyclic epoxy resin (see below).
[0155] [Chemical formula 7]
[0156]
[0157] The compound that reacts with dicyandiamide to form guanidine is preferably an aliphatic thiol compound, more preferably a tetrafunctional or higher-functional aliphatic thiol compound, and further preferably 1,3,4,6-tetrakis(2-mercaptoethyl)glycoluril and 1,3,4,6-tetrakis(3-mercaptopropyl)glycoluril.
[0158] The amount of the active hydrogen compound (B2) having a pKa exceeding 10 may be the same as in the above case 2).
[0159] (Catalyst (C2) that generates cations by reaction or light irradiation)
[0160] The catalyst (C2) that generates cations by reaction or light irradiation is a catalyst that generates cations by reaction with the above-mentioned active hydrogen compound (B2) or light irradiation.
[0161] As for the catalyst that generates a cation by reaction, after activating the active hydrogen compound (B2), it contributes to the activation of the epoxy group by carrying a positive charge, and has the same function as the cationic catalyst (C1). Examples of such catalysts include dicyandiamide, etc. By controlling the reaction with the active hydrogen compound (B2), the curing start can be controlled, so it is preferred.
[0162] Examples of catalysts that generate cations by light irradiation include photobase generators, such as carboxylate salts, salts containing borate anions, and quaternary ammonium salts.
[0163] When a carboxylate or a salt containing a borate anion is used, a strong base such as amidine, guanidine, or phosphazene base can be generated from a weak base such as an aliphatic amine compound. Therefore, the reaction with an alicyclic epoxy compound or the like easily proceeds in a chain reaction, and the curing reactivity is easily improved.
[0164] When a quaternary ammonium salt is used, it is preferred to contain imidazole or amidine as the base-reactive substance from the viewpoint of improving curing reactivity.
[0165] Among them, from the viewpoint of easily generating a strong base and easily improving the curing reactivity, preferred are (8E)-8-ethylidene-4-methoxy-5,6,7,8-tetrahydronaphthalene-1-carboxylic acid 1,8-diazabicyclo[5,4,0]undec-7-ene salt, 1,2-diisopropyl-3-[bis(dimethylamino)methylene]guanidinium 2-(3-benzoylphenyl)propionate, 1,2-dicyclohexyl-4,4,5,5-tetramethylbiguanidinium n-butyltriphenylborate, and (2-(9-oxobenzofluoren-2-yl)propionic acid-1,5,7-triazabicyclo[4,4,0]dec-5-ene salt).
[0166] The amount of catalyst (C2) used is preferably 0.5 to 10 parts by mass relative to the total amount of 100 parts by mass of the epoxy-containing compound. If the amount of catalyst (C2) used is 0.5 parts by mass or more, it is easier to activate alicyclic epoxy compounds and the like, and it is easy to obtain sufficient curing reactivity. If the amount of catalyst (C2) used is 10 parts by mass or less, it is possible to further suppress the reduction in physical properties such as glass transition temperature and elastic modulus caused by excessive residue of the catalyst in the curing resin composition. From the same viewpoint, the amount of catalyst (C2) used is more preferably 1 to 5 parts by mass relative to the total amount of 100 parts by mass of the epoxy-containing compound.
[0167] In addition, when a cationic catalyst (C2) is generated by reaction, the amount of the catalyst (C2) used is preferably 0.5 to 10 parts by mass, more preferably 1 to 5 parts by mass, relative to 100 parts by mass of the active hydrogen compound (B2). If the amount of the catalyst (C2) used is within the above range, a sufficient amount of guanidine is easily generated by reaction with the active hydrogen compound (B2), and curing reactivity is easily further improved.
[0168] In addition, when using a catalyst (C2) that generates cations by light irradiation, a sensitizer can be further used. The sensitizer has the function of increasing the sensitivity of the curing reaction. The sensitizer can be any compound that can transfer stimulating energy such as heat and light to other substances, and a sensitizer containing a naphthalene structure, anthracene structure or thioxanthone structure can be used. From the viewpoint of increasing the activity of the catalyst (C2), the mass ratio of the sensitizer to the catalyst (C2) (sensitizer / catalyst (C2)) can be, for example, 0.1 to 0.5.
[0169] In addition, when a thiol compound is used as the active hydrogen compound (B), the pot life can be extended by using a stabilizer as a curing accelerator. Examples of the stabilizer include boric acid esters such as triethyl borate, triisopropyl borate, trimethyl borate, tri-n-propyl borate, and tri-n-butyl borate.
[0170] 4) Others
[0171] In the case of the addition reaction of the epoxy group and the active hydrogen compound (iii) described above, in either case, from the viewpoint of further shortening the curing time of the resin composition containing the curing agent, it is preferred that the amount of the anhydride curing agent used is small. Specifically, the amount of the anhydride curing agent used is preferably 40 parts by mass or less, more preferably 20 parts by mass or less, and further preferably 10 parts by mass or less relative to 100 parts by mass of the resin composition containing the curing agent.
[0172] In addition, in the case of the above-mentioned (iii) addition reaction of the epoxy group with the active hydrogen compound, the case of combining the active hydrogen compound (B) with an arbitrary curing catalyst (C) is shown, but it is not limited to this, and a two-liquid curing agent-containing resin composition can also be prepared by combining a first liquid and a second liquid mixed during use.
[0173] For example, when a cationic catalyst (C1) is used, a two-liquid curing agent-containing resin composition can be prepared by combining a first liquid comprising the above-mentioned first resin composition and the cationic catalyst (C1) with a second liquid comprising an active hydrogen compound (B2). It should be noted that the above-mentioned first resin composition can be added to at least one of the first liquid and the second liquid. From the viewpoint of easy mixing, the two-liquid curing agent-containing resin composition preferably has a viscosity close to that of the first liquid and the second liquid. That is, in order to adjust the viscosity of the first liquid and the second liquid, the first resin composition can be added to both the first liquid and the second liquid.
[0174] In addition, when a catalyst (C2) is used, a two-liquid curing agent-containing resin composition can be prepared by combining a first liquid comprising the above-mentioned first resin composition with a second liquid comprising an active hydrogen compound (B2) and a catalyst (C2). From the viewpoint of easy mixing, the two-liquid curing agent-containing resin composition preferably has a first liquid and a second liquid with a viscosity close to each other. In order to adjust the viscosity of the first liquid and the second liquid, the above-mentioned first resin composition can be added to both the first liquid and the second liquid. For example, it can also be a two-liquid curing agent-containing resin composition composed of a first liquid comprising the above-mentioned first resin composition and a catalyst (C2) and a second liquid comprising the above-mentioned first resin composition and an active hydrogen compound (B2).
[0175] It should be noted that, in (iii) the addition reaction of an epoxy group with an active hydrogen compound, when a difunctional epoxy compound is used as the compound having an epoxy group in the above-mentioned first resin composition (such as an alicyclic epoxy compound), and when a difunctional compound is used as the above-mentioned active hydrogen compound (B1) or (B2), the obtained cured resin composition exhibits thermoplasticity.
[0176] Here, in the above-mentioned (i) co-condensation reaction of epoxy group and acid anhydride group, the epoxy group of alicyclic epoxy resin reacts with acid anhydride and then opens the ring to form oxyanion (—O - ), and therefore (not only the acid anhydride) also reacts with other alicyclic epoxy resins, and three-dimensional crosslinking is easily performed (refer to the following reaction scheme and reaction example 1).
[0177] [Chemical formula 8]
[0178]
[0179] [Chemical formula 9]
[0180]
[0181] In addition, (ii) self-polymerization of the epoxy group using a basic catalyst or an acidic catalyst also allows alicyclic epoxy resins to react with each other and easily form three-dimensional crosslinks.
[0182] On the other hand, in the addition reaction (iii) of the epoxy group with the active hydrogen compound, after the epoxy group of the alicyclic epoxy resin reacts with the active hydrogen compound, the cationic (H + ) and becomes -OH, so it does not react with other alicyclic epoxy resins, but only reacts with active hydrogen compounds (refer to the following reaction scheme and reaction example 2).
[0183] [Chemical formula 10]
[0184]
[0185] [Chemical formula 11]
[0186]
[0187] That is, (iii) does not react via oxygen anions, so it is difficult for alicyclic epoxy resins to react with each other, so in the addition reaction of the epoxy group and the active hydrogen compound (iii), three-dimensional crosslinking is easily suppressed compared with (i) and (ii). The less crosslinking, the higher the toughness, so the fracture toughness value of the cured resin composition obtained by the addition reaction of the epoxy group and the active hydrogen compound (iii) is easily improved.
[0188] (iv) Others
[0189] In any scheme, when the resin composition containing a curing agent is used for coatings, etc., as described above, the resin composition containing a curing agent of the present application contains cellulose fibers, etc., but has low viscosity. Therefore, it can be expected that it can be used without adding a solvent, but in the case of requiring a lower viscosity, a solvent can be further used. The amount of the solvent used is preferably 0 to 100 mass %, more preferably 0 to 50 mass %, and further preferably 0 to 20 mass % relative to the non-volatile component of the resin composition containing a curing agent.
[0190] (v) Method for producing cured resin composition
[0191] In any embodiment, the curable resin composition can be produced by heating a curing agent-containing resin composition including the first resin composition, a curing agent, etc., or by irradiating the curing agent-containing resin composition with light.
[0192] The heating temperature also depends on the types of curing agent and catalyst, but in order to suppress the decomposition of cellulose fibers in the first resin composition, it is preferably 200° C. or less, and more preferably 60° C. or more and 150° C. or less. In addition, the heating time may be short as long as it is cured, but in order to fully cure it, it is preferably 0.1 hour or more and 10 hours or less, and more preferably 0.5 hour or more and 8 hours or less.
[0193] On the other hand, when the curing agent resin composition contains a catalyst (C2) that generates cations by light, light irradiation is performed. The light irradiation conditions at this time can be any range as long as the catalyst (C2) generates a base. The wavelength of the irradiated light is preferably 200 to 500 nm, for example. In addition, the irradiation amount is preferably 10 to 10000 mJ / cm 2 After the cations are generated by light irradiation, the cations may be cured at a low temperature below room temperature, or the cations may be cured in a short time by raising the temperature to the above-mentioned heating temperature range.
[0194] (vi) Use of the curable resin composition
[0195] The thermoplastic and thermosetting curing resin compositions obtained by the above-mentioned first resin combination all comprise cellulose fibers, so have high strength. In addition, these curing resin compositions are owing to further comprising rubber particles, so toughness is also high. Therefore, the curing resin composition can be used for the purposes of the composite material that can be applied to comprise resin and reinforcing material in the past, for example various purposes such as vehicles, aircrafts such as electrification products, building materials, automobiles, trams, etc.
[0196] 4. Rubber bonding cellulose fiber
[0197] The rubber-bonded cellulose fiber of the present invention comprises cellulose fiber, a plurality of rubber particles having an average particle size of 300 nm or less arranged on the surface of the cellulose fiber, and a silane compound bonding the cellulose fiber and the rubber particles. That is, in the rubber-bonded cellulose fiber, the rubber particles are bonded to the cellulose fiber via the silane compound. This structure is confirmed, for example, by a scanning electron microscope. Generally, the affinity between rubber particles and cellulose fibers is low, and when only the rubber particles and cellulose fibers are mixed, they repel each other. Refer to the photograph of the first resin composition prepared in the embodiment described later observed by a scanning electron microscope ( Figure 3 In the first visual field of FIG. 1 , it can be seen that there is a gap between the rubber-bonded cellulose fibers and the free rubber particles, and the cellulose fibers and the rubber particles repel each other. That is, it is difficult to bond the cellulose fibers and the rubber particles simply by mixing them. In contrast, in the rubber-bonded cellulose fibers of the present invention, since the silane compound is arranged between the cellulose fibers and the rubber particles, they can be bonded.
[0198] In the rubber-bonded cellulose fibers in which rubber particles are bonded around the cellulose fibers, when dispersed in the resin, the rubber-bonded cellulose fibers are not easily entangled with each other or are not easily hydrogen-bonded. Therefore, the rubber-bonded cellulose fibers are easily and uniformly dispersed in various resins. As a result, the viscosity of the resin composition containing the resin and the rubber-bonded cellulose fibers and the melt viscosity when the resin and the rubber-bonded cellulose fibers are melt-kneaded are easily reduced. In addition, if such rubber-bonded cellulose fibers are dispersed in the resin, compared with the case of dispersing unprocessed cellulose fibers, there are also advantages that the breaking point becomes larger, the elastic modulus becomes higher, and the maximum point stress becomes higher.
[0199] Here, the type, average fiber diameter, aspect ratio, etc. of the cellulose fibers contained in the rubber-bonding cellulose fibers are the same as those of the cellulose fibers explained in the first resin composition.
[0200] In addition, the rubber particles can be particles with an average particle size of 300 nm or less, and are preferably rubber particles having carboxyl groups on the surface as described in the first resin composition. It should be noted that preferably, part or all of the carboxyl groups on the surface of the rubber particles react with the amino groups of the silane compound described later to form amide bonds. It should be noted that the rubber-bonded cellulose fibers may contain only one type of rubber particles, or may contain two or more types.
[0201] Here, the average particle size of the rubber particles is preferably 10 nm or more and 300 nm or less, and more preferably 20 nm or more and 100 nm or less. If the average particle size of the rubber particles is too small, the rubber particles are covered with the silane compound, and it is sometimes difficult to exert the characteristics of the rubber particles. On the other hand, if the average particle size is 10 nm or more, the rubber particles are easily exposed on the surface of the rubber-bonded cellulose fibers, and when mixed with the resin, the above-mentioned viscosity reduction effect is easily obtained. The above-mentioned average particle size can be determined based on JIS Z8825 as long as the rubber particles can be separated from the rubber-bonded cellulose fibers, or by directly observing / measuring the particle size of more than 100 rubber particles using a transmission electron microscope or the like.
[0202] The rubber particles are preferably uniformly arranged around the cellulose fibers. The amount (mass) of the rubber particles relative to the amount (mass) of the cellulose fibers can be appropriately selected according to the fiber diameter and fiber length of the cellulose fibers, preferably 0.1 times or more and 10 times or less, more preferably 0.2 times or more and 3 times or less. If such an amount of rubber particles is arranged around the cellulose fibers, the viscosity when mixed with the resin and the melt viscosity during melt kneading are easily further reduced.
[0203] On the other hand, the silane compound is a compound used to bond the above-mentioned cellulose fibers and rubber particles, preferably a silane coupling agent having an amino group (aminosilane coupling agent) described in the above-mentioned first resin composition. Preferably, a part or all of the amino groups contained in the aminosilane coupling agent react with the carboxyl groups of the above-mentioned rubber particles to form an amide bond. It should be noted that the rubber-bonded cellulose fibers may contain only one silane compound, or may contain two or more.
[0204] The amount (mass) of the silane compound relative to the amount (mass) of the rubber particles is preferably 0.1 times or more and 0.5 times or less, more preferably 0.2 times or more and 0.4 times or less, and further preferably 0.25 times or more and 0.35 times or less. As described above, it is preferred that the periphery of the rubber particles is not completely covered by the silane compound. Therefore, the amount of the silane compound is preferably 0.5 times or less of the amount of the rubber particles. On the other hand, it is preferred that the rubber particles are firmly bonded around the cellulose fibers, and the amount of the silane compound is preferably 0.1 times or more of the amount of the rubber particles.
[0205] 5. Method for producing rubber-bonded cellulose fibers
[0206] As a method for producing the rubber-bonded cellulose fibers, there can be cited a method including the steps of mixing a dispersion medium, rubber particles having an average particle size of 300 nm or less and having carboxyl groups on the surface, a silane compound having an amino group, and cellulose fibers to obtain a mixed solution (mixed solution preparation step); and removing the dispersion medium from the mixed solution (dispersion medium removal step). However, the method for producing the rubber-bonded cellulose fibers is not limited to this method.
[0207] (i) Mixed solution preparation process
[0208] In the mixed solution preparation step, a dispersion medium, rubber particles having an average particle size of 300 nm or less and having carboxyl groups on the surface, a silane compound having an amino group, and cellulose fibers are mixed. Thus, a dispersion liquid in which the rubber-bonded cellulose fibers are dispersed in the dispersion medium is obtained. Here, the rubber particles, silane compound, and cellulose fibers used in this step are the same as the components used in the preparation of the first resin composition.
[0209] On the other hand, as a dispersion medium used in the preparation of the mixed solution, there is no particular limitation as long as it does not react with the rubber particles, silane compounds, and cellulose fibers and can evenly disperse them. Examples of the dispersion medium include alicyclic epoxy compounds, alcohols having a relative dielectric constant of 8 to 18, and esters having a relative dielectric constant of 8 to 18.
[0210] The alicyclic epoxy compound that can be used as a dispersion medium can be the same compound as the alicyclic epoxy compound used in the first resin composition. As mentioned above, the alicyclic epoxy compound is not easy to react with the silane compound having an amino group, and can make the rubber particles uniformly dispersed. Therefore, it is suitable as a dispersion medium for the mixed solution. It should be noted that when the alicyclic epoxy compound is used as a dispersion medium, the mixed solution preparation process can be carried out in the same manner as the preparation method of the first resin composition.
[0211] In addition, at this time, the amount of the alicyclic epoxy compound used is not particularly limited as long as the rubber particles, the silane compound and the cellulose fibers can be uniformly dispersed. It is preferably 40% by mass or more and 90% by mass or less, and more preferably 50% by mass or more and 80% by mass or less relative to the total amount of the rubber particles, the silane compound and the cellulose fibers. If it is 40% by mass or more, it is easy to uniformly disperse the components. On the other hand, if it is 90% by mass or less, it is easy to remove the dispersion medium (alicyclic epoxy compound) in the dispersion medium removal step described later.
[0212] On the other hand, examples of alcohols having a relative dielectric constant of 8 or more and 18 or less at 25° C. include propylene glycol monomethyl ether, ethylene glycol monomethyl ether, isobutyl alcohol, isoamyl alcohol, o-cresol, m-cresol, p-cresol, phenol, 1-butanol, t-butyl alcohol, 1-octanol, benzyl alcohol, and the like.
[0213] Furthermore, examples of the ester having a relative dielectric constant of 8 or more and 18 or less at 25° C. include propylene glycol monomethyl ether acetate and the like.
[0214] Alcohols or esters having a relative dielectric constant of 8 or more and 18 or less at 25°C have high affinity with rubber particles, silane compounds, and cellulose fibers. Therefore, by using these alcohols and esters as dispersion media, rubber particles, silane compounds, and cellulose fibers can be uniformly dispersed, and the reaction between the amino group of the silane compound and the carboxyl group of the rubber particles, and the reaction between the silicon of the silane compound and the OH group on the surface of the cellulose fibers can be fully generated. It should be noted that, as dispersion media, the above-mentioned alcohols and esters can be used alone or in combination of two or more. For example, alcohols and esters can be used in combination.
[0215] In addition, when alcohol and / or ester are used as the dispersion medium, their total amount is preferably 4% by mass or more and 25% by mass or less, and more preferably 8% by mass or more and 11% by mass or less relative to the total amount of the cellulose fibers, rubber particles and silane compounds. If the amount of the dispersion medium is within this range, it is easier to evenly disperse the rubber particles, silane compounds and cellulose fibers.
[0216] It should be noted that, in the case where the above-mentioned dispersion medium is any one, the mixing method of the dispersion medium, rubber particles, silane compound and cellulose fiber is not particularly limited, and the mixed solution can be prepared by stirring with a known mixer. In addition, the mixing order of the dispersion medium, rubber particles, silane compound and cellulose fiber is not particularly limited, and it is more preferred to mix the silane compound and cellulose fiber in sequence while the rubber particles are dispersed in the dispersion medium. If mixed in this order, the carboxyl groups of the rubber particles in the dispersion medium react with the amines of the silane compound, and they become bonded. Then, by adding cellulose fiber, the hydroxyl groups around the cellulose fiber form siloxane bonds with the Si atoms of the silane compound, and the rubber particles are arranged around the cellulose fiber.
[0217] It should be noted that, when mixing the components, heating may be performed in order to promote the above reaction. The upper limit temperature varies depending on the boiling point of the dispersion medium, but when heating is performed, the temperature is preferably 40° C. or higher and 140° C. or lower, more preferably 60° C. or higher and 120° C. or lower. Furthermore, the time is preferably 10 minutes or higher and 120 minutes or lower, more preferably 20 minutes or higher and 60 minutes or lower.
[0218] (ii) Dispersion Medium Removal Step
[0219] After the preparation of the mixed solution (dispersion solution of rubber-bonded cellulose fibers), the dispersion medium is removed from the mixed solution. The method for removing the dispersion medium can be appropriately selected depending on the type of the dispersion medium.
[0220] In the case where the dispersion medium is an alicyclic epoxy compound, it is preferred to use various solvents to dissolve the alicyclic epoxy compound. As the solvent used, any component that does not deteriorate the rubber-bonded cellulose fiber and can only dissolve the alicyclic epoxy compound is sufficient. Examples of the solvent include alcohols with a relative dielectric constant of 8 or more and 18 or less, such as propylene glycol methyl ether, and esters with a relative dielectric constant of 8 or more and 18 or less, such as propylene glycol monomethyl ether acetate. They are not easy to agglomerate rubber particles, and they also have affinity with alicyclic epoxy resins. Therefore, by using them as solvents, alicyclic epoxy resins can be fully rinsed without deteriorating the rubber-bonded cellulose fibers. Among them, propylene glycol methyl ether is particularly preferred from the perspectives of ease of acquisition, solubility of alicyclic epoxy compounds, etc. After the above-mentioned alicyclic epoxy compound is dissolved, filtering can be cited as a method for separating the rubber-bonded cellulose fibers, but it is not limited to this. In addition, after the rubber-bonded cellulose fibers are separated, a process of further washing or drying them can also be performed.
[0221] On the other hand, when the dispersion medium is the alcohol or ether, the rubber-bonded cellulose fibers can be separated by removing the dispersion medium through filtration, drying, etc. In this case, after the rubber-bonded cellulose fibers are separated, a step of further washing or drying them may be performed.
[0222] In addition, like the above-mentioned first resin composition, the rubber-bonded cellulose fibers may be dispersed in a dispersion medium and used for various purposes as they are without performing the dispersion medium removal step.
[0223] 6. Second resin composition
[0224] The second resin composition of the present invention is a composition comprising a resin and a fibrous composite derived from the above-mentioned rubber-bonded cellulose fibers.
[0225] The resin comprising the second resin composition may be a thermosetting resin or a thermoplastic resin. Examples of thermosetting resins include epoxy resins, polyurethane resins, phenolic resins, and the like. In view of the heat resistance of the rubber-bonded cellulose fibers, a resin that can be mixed at a temperature below 200°C is preferred, for example, a resin that is liquid at room temperature or has a softening point below 200°C, more preferably a bisphenol A epoxy resin, a bisphenol F epoxy resin, an alicyclic epoxy resin, and the like. In the case where the resin is a thermosetting resin, the second resin composition may further include a curing agent.
[0226] On the other hand, examples of thermoplastic resins include polyolefin resins such as polyethylene resins and polypropylene resins, polyester resins, polyamide resins, etc. Among them, polyethylene resins and polypropylene resins having relatively low melting points are preferred.
[0227] In either case where the resin is a thermosetting resin or a thermoplastic resin, the content of the resin relative to the total amount of the second resin composition (the non-volatile component of the second resin composition when the second resin composition contains a volatile component) is preferably 40% by mass or more and 99.5% by mass or less, and more preferably 50% by mass or more and 99% by mass or less. If the amount of the resin is within this range, the strength of the resin composition is easily improved and can be easily used for various purposes.
[0228] On the other hand, the fibrous composite contained in the second resin composition can be derived from the above-mentioned rubber-bonded cellulose fibers, and can be the above-mentioned rubber-bonded cellulose fibers themselves, or can be a fibrous composite having a coating derived from the above-mentioned rubber particles formed around the cellulose fibers, etc. When preparing the second resin composition, if melt kneading is performed near the softening point of the rubber, the rubber particles soften and such a coating is easily formed.
[0229] The amount of the fibrous composite derived from the rubber-bonded cellulose fiber is preferably 0.5% by mass or more and 60% by mass or less relative to the total amount of the second resin composition (when the second resin composition contains a volatile component, it is the non-volatile component of the second resin composition), and more preferably 1% by mass or more and 50% by mass or less. If the amount of the fibrous composite is 60% by mass or less, the amount of the resin becomes sufficient, and it is easy to obtain the original fluidity and other characteristics of the resin. On the other hand, if the amount of the fibrous composite is 0.5% by mass or more, the elastic modulus of the resin composition is easily further improved, and it is easy to become difficult to break compared with the material of the same elastic modulus.
[0230] The second resin composition may contain other components in addition to the resin and the rubber-bonding cellulose fibers within a range that does not impair the object and effect of the present invention. Examples of other components include solvents, curing agents, various additives, and the like.
[0231] In addition, the preparation method of the second resin composition can be appropriately selected according to the type of resin. For example, when the resin is liquid at room temperature, the resin, the rubber-bonded cellulose fiber, and other components as needed can be mixed at a relatively low temperature to prepare. On the other hand, when the resin is solid at room temperature, the resin, the rubber-bonded cellulose fiber, and other components as needed can be mixed and mixed by melt kneading or the like.
[0232] The above-mentioned second resin combination has high strength because it comprises cellulose fiber together with various resins. In addition, these resin combinations have high toughness because they further comprise rubber particles. Therefore, the second resin combination can be used for the purposes of the composite material that can be applied to comprise resin and reinforcing material in the past, such as various purposes such as vehicles, aircrafts such as electrified products, building materials, automobiles, trams, etc.
[0233] Example
[0234] Hereinafter, the present invention will be further described with reference to Examples and Comparative Examples, but the technical scope of the present invention is not limited thereto.
[0235] 1. Preparation of Materials
[0236] The following materials were prepared.
[0237] (Epoxides)
[0238] Alicyclic epoxy compound (a compound represented by the following formula, Celloxide 2021P, manufactured by Daicel Corporation).
[0239] [Chemical formula 12]
[0240]
[0241] Bisphenol A type epoxy compound (EPCLON850S, manufactured by DIC Corporation).
[0242] (Cellulose Fiber)
[0243] Cellulose fiber A (KC flock W-50GK, manufactured by Nippon Paper Industries, Ltd., average particle size (catalog value): 45 μm, viscosity measured by the following method: 72.1 Pa·s).
[0244] Cellulose fiber B (ARBOCEL BE600-10 TG, manufactured by RETTENMAIER JAPAN CO., LTD., average fiber length (catalog value): 18 μm, viscosity measured by the following method: 6.9 Pa·s).
[0245] Cellulose fibers C (ARBOCEL UFC100, manufactured by RETTENMAIER JAPAN CO., LTD., average fiber length (catalog value): 6 to 12 μm, viscosity measured by the following method: 7.9 Pa·s).
[0246] Cellulose fiber D (KC flock W-400GK, manufactured by Nippon Paper Industries, Ltd., average particle size (catalog value): 24 μm, viscosity measured by the following method: 14.1 Pa·s).
[0247] <Method for measuring viscosity of cellulose fibers>
[0248] Cellulose fiber was added to RKB-5810 (manufactured by Resinous Kasei Co., Ltd.), a highly transparent rubber-modified epoxy resin, and the concentration was adjusted with Celloxide 2021P (manufactured by Daicel Co., Ltd.), an alicyclic epoxy resin, so that the rubber particle concentration was 8% by mass and the cellulose fiber concentration was 8% by mass. The viscosity of the dispersion was measured (values at 25°C, 5 rpm, and 30 seconds) using a cone-plate viscometer (TVE-35H, cone rotor: 3°×R9.7, manufactured by Toki Sangyo Co., Ltd.).
[0249] (Rubber particles)
[0250] A bifunctional alicyclic epoxy resin containing 10% by mass of rubber particles (RKB-5810, manufactured by Resinous Kasei Co., Ltd., average particle size of rubber particles: several tens of nanometers, core-shell type rubber particles, having carboxyl groups on the surface).
[0251] A bifunctional alicyclic epoxy resin containing 20% by mass of rubber particles (RKB-5820, manufactured by Resinous Kasei Co., Ltd., average particle size of rubber particles: several tens of nanometers, core-shell type rubber particles, having carboxyl groups on the surface).
[0252] Rubber particles (Staphyloid AC3832SD, manufactured by AICA, average particle size: 500 nm, core-shell type rubber particles, having carboxyl groups on the surface).
[0253] Propylene glycol monomethyl ether containing 4.3% by mass of rubber particles (RKB-8818, manufactured by Resinous Kasei Co., Ltd., average particle size of rubber particles: several tens of nanometers, core-shell type rubber particles, having carboxyl groups on the surface).
[0254] (Silane coupling agent)
[0255] Aminosilane coupling agent (aminopropyltriethoxysilane, DOWSIL Z-6011, manufactured by DOW Corporation).
[0256] · Epoxy silane coupling agent (glycidoxypropyltrimethoxysilane, XIAMETER OFS-6040, manufactured by DOW).
[0257] (Curing agent)
[0258] Acid anhydride (4-methylhexahydrophthalic anhydride / hexahydrophthalic anhydride, Rikacid MH-700, manufactured by Shin Nippon Rika Co., Ltd.).
[0259] ·Difunctional aromatic thiol (4,4'-thiobisbenzenethiol).
[0260] Catalyst (2-ethyl-4-methylimidazole, manufactured by Shikoku Chemicals Co., Ltd.).
[0261] 2. Preparation of the First Resin Composition and the Cured Resin Composition
[0262] [Example 1]
[0263] 97.6 g of an alicyclic epoxy resin (RKB-5810) containing 10% by mass of rubber particles, 12.2 g of an alicyclic epoxy compound (CELLOXIDE 2021P), and 3.4 g of an aminosilane coupling agent (Z-6011) were mixed, and then stirred at 2000 rpm for 30 seconds using an Awatori Rentaro (normal pressure type, ARE-310) to disperse the silane coupling agent in the resin.
[0264] Then, cellulose fiber A (KC Flock W-50GK) was added in an absolute dry weight of 9.8 g and dispersed with a ceramic roller until the particle size was less than 50 μm (twice (about 10 minutes)). After heating the composition at 60° C. for 1 hour, it was mixed with Awatori Rentaro (vacuum type, ARV-310P) at 2000 rpm and 0.8 kPa for 300 seconds for defoaming to obtain a first resin composition.
[0265] In addition, 1.0 g of the catalyst (2E4MZ) and 120.0 g of anhydride (MH700) which had been dissolved by heating were mixed, and then mixed with the first resin composition, and the mixture was mixed with Awatori Rentaro (vacuum type, ARV-310P) at 2000 rpm and 0.8 kPa for 100 seconds for defoaming to obtain a resin composition containing a curing agent.
[0266] [Examples 2 to 11]
[0267] A first resin composition and a curing agent-containing resin composition were prepared in the same manner as in Example 1 except that the composition was changed to the composition shown in Table 1 below.
[0268] [Example 12]
[0269] The first resin composition was prepared by the same method as in Example 1. Then, 4,4′-thiobisbenzenethiol was further added to the first resin composition, and mixed in the same manner as in Example 1 to obtain a curing agent-containing resin composition.
[0270] [Comparative Examples 1 to 12]
[0271] Except having changed into the composition shown in Table 2, it carried out similarly to Example 1, and prepared the resin composition and the resin composition containing a curing agent.
[0272] [Reference Examples 1 and 3]
[0273] The alicyclic epoxy compound or the bisphenol epoxy compound is used alone.
[0274] [Reference Examples 2 and 4]
[0275] As shown in Table 3, the alicyclic epoxy compound or the bisphenol epoxy compound is mixed with the aminosilane coupling agent.
[0276] [Reference Examples 5 to 7]
[0277] Except having changed the composition as shown in Table 3, a resin composition and a resin composition containing a curing agent were prepared in the same manner as in Example 1.
[0278] [evaluate]
[0279] Evaluation of bending test
[0280] The resin composition containing the curing agent obtained in the above-mentioned embodiment and the comparative example is injected into a casting plate formed by sandwiching a 3mm thick rubber spacer with a glass plate, heated at 90°C for 3 hours, heated to 120°C in 6 minutes, and thermally cured at 120°C for 4 hours. The obtained cured product is cut into a size of 10mm wide and 80mm long, and used as a test piece. Using a precision universal testing machine (manufactured by Shimadzu Corporation, AUTOGRAPH AG-X plus), the bending modulus of the test piece is measured according to JIS K6911. The larger the value, the higher the bending strength. The results are shown in Tables 1 and 2.
[0281] Evaluation of viscosity
[0282] The viscosity X (value at 25°C, 5 rpm, 30 seconds) of the first resin composition (or resin composition) excluding the curing agent and the catalyst of the above-mentioned examples and comparative examples was measured using a cone-plate viscometer (TVE-35H, conical rotor: 3°×R9.7, manufactured by Toki Sangyo Co., Ltd.). In addition, the composition was prepared in the same manner as in the examples and comparative examples except that no silane coupling agent was added, and the viscosity Y of the composition without the silane coupling agent was measured in the same manner as above. Then, viscosity X-viscosity Y was determined. The results are shown in Tables 1 and 2. It should be noted that for Reference Examples 1 to 4, the viscosity just after mixing and the viscosity after standing at 60°C for 1 hour were measured. The results are shown in Table 3. It should be noted that their viscosities were measured in the same manner as above except that the rotation speed was set to 50 rpm.
[0283] Determination of fracture toughness value
[0284] The resin composition containing the curing agent obtained in the above-mentioned examples and comparative examples was injected into a casting plate formed by sandwiching a 6 mm thick rubber spacer between glass plates, heated at 90°C for 3 hours, then heated to 120°C over 6 minutes, and thermally cured at 120°C for 4 hours. The obtained cured product was cut into a size of 12.5 mm wide × 80 mm long to obtain a test piece. The test piece was further processed according to ASTM D5045 and the fracture toughness (unit: MPa·m 0.5 ) is measured. The precrack is made on the test piece by placing a blade on the notch of the test piece and hitting the blade with a hammer. The higher the value, the better. For example, it is preferably 0.6 or more, and more preferably 1.0 or more. The results are shown in Tables 1 to 3.
[0285] Measuring machine: Shimadzu Autoplotter (manufactured by Shimadzu Corporation).
[0286] Model:AG-X plus.
[0287] Test speed: 0.5 mm / min.
[0288] Span distance: 50mm. Thermoplastic test
[0289] The curing agent-containing resin compositions prepared in Examples 1 and 12 were respectively injected into a casting plate having a 1 mm thick rubber spacer sandwiched between glass plates. The curing agent-containing resin composition of Example 1 was heated at 90° C. for 3 hours, then heated to 120° C. over 6 minutes and thermally cured at 120° C. for 4 hours. The curing agent-containing resin composition of Example 13 was thermally cured at 100° C. for 1 hour.
[0290] The obtained solidified products were placed in an oven heated to 200°C in a state of being upright with clips, and the shape after 1 minute was confirmed. Then, if the shape before placement was not maintained, it was judged to be thermoplastic. The state before placement in the oven is shown in FIG. Figure 1 , the state after being put into the oven is shown in Figure 2 .like Figure 1 and Figure 2 As shown, only Example 12 exhibits thermoplasticity.
[0291] Observation of cured resin composition
[0292] A photograph of the cured resin composition prepared in Example 1 observed with a scanning electron microscope (SEM) is shown in FIG. Figure 3 .like Figure 3 As shown, in the cured resin composition, the rubber particles are bonded to the periphery of the cellulose fibers via the silane compound.
[0293] [Table 1]
[0294]
[0295]
[0296] [Table 2]
[0297]
[0298]
[0299] [Table 3]
[0300]
[0301] As shown in Table 1, in the first resin composition containing an alicyclic epoxy compound, cellulose fibers, carboxyl group-containing rubber particles and an aminosilane coupling agent, the viscosity of the first resin composition was reduced by adding the aminosilane coupling agent (Examples 1 to 12).
[0302] On the other hand, as shown in Table 2, in Comparative Examples 1 to 6 and 8 to 10 in which no silane coupling agent was added, the viscosity of the resin composition was high compared to the examples having the same cellulose fiber content and rubber particle content. In addition, in Comparative Example 11 in which an epoxy silane coupling agent was used instead of an amino silane coupling agent, the viscosity increased by adding a silane coupling agent. Furthermore, even if an amino silane coupling agent was used, in Comparative Example 7 in which carboxyl-containing rubber particles having a predetermined average particle size were not included, the viscosity of the resin composition was very high, and the viscosity was further increased by adding an amino silane coupling agent. In addition, in Comparative Example 12 in which rubber particles having a large average particle size were used, the viscosity was also increased by adding an amino silane coupling agent.
[0303] It should be noted that, when compared with Reference Examples 1 and 2, even if an aminosilane coupling agent is added to an alicyclic epoxy resin, the viscosity hardly changes by accelerating the reaction by heating. On the other hand, in Reference Example 4, if an aminosilane coupling agent is added to a bisphenol A epoxy resin, the viscosity increases. In Reference Examples 5 to 7, in which only the amount of rubber particles is increased, although the fracture toughness value increases, the result is still lower than that of Examples 1 to 11 in which rubber particles, cellulose fibers, and an aminosilane coupling agent are used in combination.
[0304] In addition, the viscosity of Comparative Example 1 using cellulose fiber A is higher than that of Comparative Examples 9 and 10 using cellulose fibers B and C, and therefore the aspect ratio is high. In Examples 1 and 4 using cellulose fiber A and an aminosilane coupling material / carboxyl group-containing rubber particle amount of 0.25 to 0.35, the fracture toughness value is greater than 1 on the basis of reducing the viscosity to less than 2 / 3, and both toughness and viscosity reduction are achieved. 3. Preparation of rubber-bonded cellulose fiber and second resin composition
[0305] [Example a]
[0306] The first resin composition was prepared in the same manner as in Example 1. 3 times the amount of DOWANOL (registered trademark of Dow Chemical Company) PM (propylene glycol methyl ether) as a solvent was injected into the first resin composition and stirred. Then, decantation was performed and repeated 10 times until the turbidity disappeared. The obtained residual liquid was naturally filtered with filter paper 3C, and the filtrate was dried at 105°C for 8 hours to obtain rubber-bonded cellulose fiber a.
[0307] The rubber-bonded cellulose fiber a and polypropylene (MA3, Japan Polypropylene Co., Ltd.) were manually mixed to a content of 5% by mass of the rubber-bonded cellulose fiber a. The mixture was then fed into a raw material supply section of a twin-screw extruder at a barrel temperature of 180°C and melt-kneaded under conditions of an extrusion rate of 500 g / hour and a screw speed of 15 rpm to obtain particles of a second resin composition. A photograph of the particles observed with a scanning electron microscope is shown in Figure 4 .
[0308] [Example b]
[0309] 2 g of an aminosilane coupling agent (Z-6011) (0.33 times the amount of the rubber particles) was added to 140 g of propylene glycol monomethyl ether (RKB-8818) containing 4.3% by mass of rubber particles, and the mixture was stirred at room temperature using a homogenizer 2.5 to disperse the aminosilane coupling agent. 6 g of cellulose fiber D was added to the dispersion, and the mixture was heated and stirred at 60° C. for 120 minutes using a homogenizer 2.5. Then, the mixture was filtered using PTFE filter paper PF060, and the filtrate was dried at 100° C. for 4 hours to obtain rubber-bonded cellulose fibers. The photographs of the cellulose fiber D alone and the obtained rubber-bonded cellulose fiber b are shown in FIG. Figure 5 .like Figure 5 As shown in FIG. 1 , in the obtained rubber-bonded cellulose fibers b, rubber particles are bonded around the cellulose fibers.
[0310] The rubber-bonding cellulose fibers b and polypropylene (MA3, Japan Polypropylene Co., Ltd.) were mixed so that the content of the rubber-bonding cellulose fibers b was 5% by mass, and particles of a second resin composition were obtained in the same manner as in Example a.
[0311] [Comparative Example a]
[0312] Cellulose fiber A and polypropylene (MA3, Japan Polypropylene Co., Ltd.) were mixed so that the content of cellulose fiber A was 5% by mass, and particles of a resin composition were obtained in the same manner as in Example a.
[0313] [Comparative Example b]
[0314] Except having changed cellulose fiber A into cellulose fiber D, it carried out similarly to the comparative example a, and obtained the particle|grains of the resin composition.
[0315] [Reference example]
[0316] Polypropylene (MA3 manufactured by Japan Polypropylene Co., Ltd.) was fed into a raw material supply section of a twin-screw extruder at a barrel temperature of 180° C. and melt-kneaded at an extrusion rate of 500 g / hour and a screw rotation speed of 15 rpm to obtain polypropylene pellets.
[0317] [evaluate]
[0318] (Melt viscosity of resin composition)
[0319] About 20 g of the resin composition was used to measure the melt viscosity of the resin composition prepared in Examples a and b and Comparative Examples a and b using Capillograph 1-C manufactured by Toyo Seiki Seisakusho. At this time, the capillary used a flat die of 1 mmφ×10 mmL and the set temperature was set to 190°C. The polymer sample was introduced into the device and kept for 5 minutes, and the shear rate was measured at 1200 sec. -1 The results are shown in Tables 4 and 5.
[0320] (Physical Properties of Resin Composition)
[0321] Tensile test (A12 type)
[0322] Using an injection molding device with an injection molding temperature of 190°C, a JIS K7139A12 type tensile test dumbbell (total length 75mm×width 5-10mm×thickness 2mm) was made from the particles of the second resin composition (or resin composition, polypropylene) prepared in the above-mentioned Examples a, b, Comparative Example a and Reference Example. Then, for the dumbbell, a precision universal testing machine ("AUTOGRAPHAG-Xplus" manufactured by Shimadzu Corporation) was used to measure the elastic modulus (corresponding to the slope of the stress / strain curve between the two strain points of ε1=0.05% and ε2=0.25%), breaking point, breaking point strain, maximum point stress, maximum point strain, upper yield point stress, and upper yield point strain of the test piece at a test speed of 10mm / min. The results are shown in Table 4.
[0323] [Table 4]
[0324]
[0325] Tensile test (Type 1A), Charpy impact test
[0326] Using an injection molding device with an injection molding temperature of 190°C, a JIS K7139 A1 type tensile test dumbbell (total length 150 mm × width 10-20 mm × thickness 4 mm) was prepared from the particles of the second resin composition (or resin composition, polypropylene) prepared in the above-mentioned Example b, Comparative Example b, and Reference Example. Then, for the dumbbell, a precision universal testing machine ("AUTOGRAPHAG-Xplus" manufactured by Shimadzu Corporation) was used to measure the elastic modulus (corresponding to the slope of the stress / strain curve between the two points of ε1=0.05% and ε2=0.25% strain) and the upper yield point stress of the test piece at a test speed of 10 mm / min. Furthermore, a test piece of a specified size (length 80 mm, notch depth 2 mm, thickness 4.0 mm, notch R0.25 mm) was formed from the molded body, and the notched test piece was subjected to a Charpy impact test at room temperature according to SO179-1 to measure the Charpy impact value (impact strength). The results are shown in Table 5.
[0327] [Table 5]
[0328]
[0329] As shown in Tables 4 and 5, the elastic modulus and upper yield stress of Examples and Comparative Examples containing cellulose fibers (unprocessed) and rubber-bonded cellulose fibers were higher than those of the case of using propylene alone (reference example).
[0330] In addition, compared with the resin composition of Comparative Example a in which cellulose fiber A (unprocessed) is added to polypropylene, the melt viscosity of the resin composition of Example a in which rubber-bonded cellulose fiber is added is low. Furthermore, it can be seen that Example a is superior to Comparative Example a in elastic modulus, breaking point, maximum point stress, etc. It is believed that the rubber-bonded cellulose fiber is uniformly dispersed in the resin composition. In addition, in Example b, the elastic modulus is also increased and the breaking point is large.
[0331] On the other hand, as shown in Table 5, when the comparative example b in which cellulose fiber D (unprocessed) is added to polypropylene is compared with the example b in which rubber-bonded cellulose fiber is added, the melt viscosity of the example b is low. In addition, it can be seen that the elastic modulus and impact strength of the example b are superior to those of the comparative example b. It is believed that the rubber is bonded to the periphery of the cellulose fiber on the basis of the uniform dispersion of the rubber-bonded cellulose fiber in the resin composition.
[0332] [Example c]
[0333] Rubber-bonded cellulose fiber a was prepared in the same manner as in Example a. Then, 10 parts by mass of rubber-bonded cellulose fiber a was added to 100 parts by mass of bisphenol A epoxy compound (EPCLON850S). Then, defoaming was performed by stirring at 2000 rpm / 0.8 kPa / 100 seconds using a vacuum Rentaro ARV-310P. The viscosity (25°C, 5 rpm, 30 seconds) of the obtained epoxy resin composition (second resin composition) was measured using a cone-plate viscometer (TVE-35H, cone rotor: 3°×R9.7, manufactured by Toki Sangyo Co., Ltd.) and the result was 47.2 Pa·s.
[0334] [Comparative Example c]
[0335] An epoxy resin composition was obtained in the same manner as in Example C except that the rubber-bonding cellulose fiber a was replaced with (unprocessed) cellulose fiber A. The viscosity of the epoxy resin composition was measured using a cone-plate viscometer (TVE-35H, cone rotor: 3°×R9.7, manufactured by Toki Sangyo Co., Ltd.) and found to be 132.6 Pa·s.
[0336] [evaluate]
[0337] Comparison of the viscosities of Example c and Comparative Example c shows that the viscosity of Example c is less than half, and that the viscosity of the resin composition can be reduced by using rubber to bond the cellulose fibers a.
[0338] This application claims the priority based on Japanese Patent Application No. 2022-138436 filed on August 31, 2022. The contents described in the above application specification and drawings are all cited in the present application specification.
[0339] Industrial Applicability
[0340] Although the resin composition of the present invention comprises epoxy compound and cellulose fiber, the viscosity can be suppressed in a relatively low range. Therefore, the operability is good and it is easy to be used for various purposes. In addition, the strength of the curable resin composition obtained by curing the resin composition is high and the toughness is also high. Therefore, it can be used for various purposes such as vehicles such as electrical products, building materials, automobiles, trams, and aircraft.
Claims
1. A rubber-bonded cellulose fiber, comprising: Cellulose fibers; a plurality of rubber particles having an average particle size of 300 nm or less and disposed on the surface of the cellulose fiber; and A silane compound that bonds the cellulose fibers and the rubber particles.
2. The rubber-bonded cellulose fiber according to claim 1, wherein The rubber particles have an average particle size of 10 nm or more and 100 nm or less.
3. A resin composition comprising: a resin and a fibrous composite derived from the rubber-bonded cellulose fiber according to claim 1 or 2.
4. The resin composition according to claim 3, wherein The resin is a thermoplastic resin.
5. The resin composition according to claim 3, wherein The resin is a polyethylene resin and / or a polypropylene resin.
6. A resin composition, comprising: Alicyclic epoxy compounds; Cellulose fibers; Rubber particles having carboxyl groups on the surface and having an average particle size of 300 nm or less; and A silane compound having an amino group.
7. The resin composition according to claim 6, wherein The content of the cellulose fibers is 1% by mass or more and 10% by mass or less.
8. The resin composition according to claim 6 or 7, wherein The content of the rubber particles is 2 mass % or more and 20 mass % or less.
9. The resin composition according to any one of claims 6 to 8, wherein The content of the silane compound is 0.1 times or more and 0.5 times or less of the content of the rubber particles.
10. The resin composition according to any one of claims 6 to 9, wherein The rubber particles have an average particle size of 10 nm or more and 100 nm or less.
11. The resin composition according to any one of claims 6 to 10, wherein The alicyclic epoxy compound has two alicyclic epoxy groups. 12 . A curable resin composition obtained by curing the alicyclic epoxy compound of the resin composition according to claim 11 with a difunctional active hydrogen compound.
13. A method for producing a resin composition, comprising: A step of mixing an alicyclic epoxy compound, rubber particles having an average particle size of 300 nm or less and having carboxyl groups on the surface, and a silane compound having an amino group; as well as The step of further mixing cellulose fibers.
14. A method for producing rubber-bonded cellulose fibers, the method comprising: A step of mixing a dispersion medium, rubber particles having an average particle size of 300 nm or less and having carboxyl groups on the surface, a silane compound having an amino group, and cellulose fibers to obtain a mixed solution; and A step of removing the dispersion medium from the mixed liquid.
15. The method for producing rubber-bonded cellulose fibers according to claim 14, wherein: The dispersion medium is an alicyclic epoxy compound.
16. The method for producing rubber-bonded cellulose fibers according to claim 15, wherein: In the step of removing the dispersion medium, the alicyclic epoxy compound is dissolved in a solvent.
17. The method for producing rubber-bonded cellulose fibers according to claim 14, wherein: The dispersion medium is an alcohol having a relative dielectric constant of 8 to 18 at 25°C and / or an ester having a relative dielectric constant of 8 to 18 at 25°C.
Citation Information
Patent Citations
Resin composition, fiber-reinforced composite material and molded part
JP2015048375A